An environmental-friendly reagent system for the flotation separation of fluorite from calcite or quartz - Wen-Yu Li; Ping Zhu; Biao Chen; Zhen-Jiang Wang; Jia-Lu Li; Yong-Chun Luo (Minerals Engineering, 2026)

Seasonally driven ecological adaptation in sea cucumbers Apostichopus japonicus: dynamic coupling of nutrient metabolism and gut microbial network reconfiguration - Ping Li; Jia-Ming Zhang; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Zhi-Hua Li (Reviews in Fish Biology and Fisheries, 2026)

Beyond gastroenteritis: first evidence of systemic biochemical disturbances, predominantly coagulation dysfunction, in Neoboletus poisoning - Jia Li; Yuan-Tian Lu; Xiu-Juan Li; Ming Li; Ping Wei; Tai-Jie Yu; Yu-Xian Gao; Ting Li; Yuan-Yuan Xiong; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Genetic diversity and distribution pattern of three economically important species of Bangiaceae (Rhodophyta) along China's coast revealed by rbcL - Meng-Xue Xu; Jia-Qiu Pu; Wei Zhou; Cui-Cui Tian; Guang-Ping Xu; Li-En Yang (Estuarine, Coastal and Shelf Science, 2026)

Overcoming thermodynamic limitations on anaerobic methanogenesis via DSF/c-di-GMP enhanced indirect interspecies electron transfer - Chunyan Li; Jia Meng; He-Ping Zhao; Ang Li (Water Research, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Hydrometeorological thresholds controlling soil carbon, nitrogen, and vegetation productivity dynamics in an Inner Mongolian grassland watershed (1981–2019) - Ge Gao; Jia Liu; Limin Duan; Yixuan Wang; Yicheng Wang; Jianzhu Li; Ping Feng; Josep Peñuelas (CATENA, 2026)

Development of a gravity-driven self-centering rubber bearing for seismic isolation - Hong-Tai Zhang; Bing Zhao; Ping Xiang; Xue-Bin Ren; Yang Li; Li-Sheng Luo; Liang-Jiu Jia (Soil Dynamics and Earthquake Engineering, 2026)

Chenietains A-G, undescribed phenylpropanoid-related compounds from Cheniella touranensis and their cytotoxic potential in vitro - Xing-Ping Zhang; Yun Wang; Jia-Le Wang; Wu-Yan Chen; Wen-Jie Ma; Yan-Heng Zhou; Ming-Ming Li; Kou Wang (Phytochemistry, 2026)

Isoprenylated phenolic derivatives from Corethrodendron scoparium and their anti-triple negative breast cancer activity - Yuan Gao; Ping Hai; Hai-Yan Jia; Mei-Ling Yang; Hui-Xia Fan; Jin Yang; Xian-Yan Li; Lian Yang; Zhi-Qiang Luo; Jian Yang (Phytochemistry, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Improving the efficiency of a bioaerosol disinfection reactor by using ultraviolet C light-emitting diodes and titanium dioxide photocatalyst - Chien-Ping Wang; Bo Yu Liao; Fan-Chun Hsieh; Qiang Jia; Tien-Li Chang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Two Contributions to the Hypogeous Boletales of China: A Novel Rhizopogon Species and a New National Record of Turmalinea persicina - Jia Li; Chang Xu; Tai‐Jie Yu; Wen‐Hao Zhang; Xiu‐Juan Li; Yu‐Xian Gao; Yuan‐Tian Lu; Li‐Ping Tang (New Zealand Journal of Botany, 2026)
Hypogeous Boletales are ectomycorrhizal fungi with sequestered hymenophores; some species are ecologically valuable as edible mushrooms. Despite their ecological and economical importance, the diversity of this group in China remains poorly understood. In this study, we performed phylogenetic analyses based on four loci (ITS, LSU, TEF1‐α , and RPB2 ) and detailed morphological examinations of specimens belonging to Rhizopogon (Rhizopogonaceae) and Turmalinea (Boletaceae). We describe and illustrate R. sinoevadens , a new species from China, and report the first Chinese record of T. persicina , a species originally described from Japan. These discoveries underscore the previously underestimated diversity of hypogeous Boletales in China and provide a foundation for future taxonomic and ecological studies.

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Can heavy metal accumulation in crops be mitigated by microbial inoculants? A meta-analysis and machine learning - Xunzhe Yang; Yunjie Li; Ping Yun; Dongqing Jia; Natasa Hulak; Yinglong Chen; Sergey Shabala; Geng Sun (Journal of Hazardous Materials, 2026)

Dual-functional Z‑scheme heterojunction nanozymes with surface encapsulation of porphyrin-based metal-organic framework on covalent organic framework for integrated detection and removal of aflatoxin B1 in foods - Birou Wang; Xiang Li; Xi Huang; Shucong Mo; Jia Yin; Bowen Chen; Yun Huang; Ping Du; Sufang He (Journal of Hazardous Materials, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Source-specific oxidative potential and health risks of PM2.5-bound toxic elements in Xiamen Port: Insights into ship emission contributions - Si-Min Zhao; Qi-Yu Miao; Jia-Min Li; Xin-Ye Wu; Bing-Qi Jiang; Li-Xiong He; Yi-Jing Liu; Zhi Huang; Chung-Shin Yuan; Shui-Ping Wu (Atmospheric Pollution Research, 2026)

A AIE Probe for Visual Monitoring of Endogenous and Exogenous H2S and Food Freshness - Rongqi Wang; Si Chen; Yamin Li; Tuotuo Fang; Zhan-Bin Jin; Ting-Ting Wei; Jia-Ping Li; Hai-Xian Ren; Zi-Ao Zong; Na-Na Li (Journal of Fluorescence, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Ion trapping as an intrinsic physicochemical barrier limiting plant translocation and phytotoxicity of ionizable contaminants - Zhi-Yu Lu; Jia-Heng Zhao; Li Yuan; Yan-Yun Hu; Yi Hu; Cheng-Yuan Liu; Yang Pan; Chun-Chun Lv; Ke-Ke Qi; Wei Zhi; Guo-Ping Sheng (Journal of Environmental Sciences, 2026)

Unravelling flavor formation in Chinese steamed bread made with fermented glutinous rice wine dough: insights from microbial succession, metabolomics, and volatile profiling - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Research International, 2026)

Temperature-dependent regulation of benzeneacetaldehyde formation during black tea drying: Evidence from non-targeted metabolomics and an EGCG-modulated Maillard reaction model - Zisheng Han; Shengxiao Su; Wen Li; Tong Jia; Piaopiao Long; Jia-Ping Ke; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

A Study on the Suitability of Operating Strategies for PV/T-Medium-to-Deep-Ground-Source Heat Pump Heating Systems Based on Peak-and-Off-Peak Electricity Rates - Dong Wei; Yu-ping Zhang; Quan-hui Liu; Yi-chao Zhao; Hao Wu; Sheng-ji Xu; Yu Cao; Jia-yuan Li; Ling-ling Bao (Applied Geophysics, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Sustainable recovery and direct regeneration of cathode materials from spent lithium-ion batteries: A critical review of green technologies - Zhengyi Ouyang; Xuetian Li; Yong Cui; He Liu; Jia Li; Zhongcai Shao; Ping Zhao (Resources, Conservation and Recycling, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Unified strength prediction formula for axially compressed FRP-confined concrete stub columns with different cross sections - Wei-Jie Li; Jing Sun; Wei-Ping Zhao; Jia-Qi Yang; Yi-Yan Lu (Engineering Structures, 2026)

Tailored pore engineering in crystalline COF membranes via trimesoyl chloride cross-linking for high-performance pharmaceutical nanofiltration in water treatment - Hao Wang; Lian You; Jian-wei Jia; Yi Wang; Li-ping Yue; Fan-xin Kong (Chemical Engineering Journal, 2026)

Characterization of a new diterpenoid glycoside and chemotaxonomical significance of secondary metabolites from Excoecaria acerifolia - Na-Li Song; Jia-Peng Wang; Li-Ping Yang; Sheng-Qi Zhang; Xia Zhao; Le Cai; Zhong-Tao Ding (Biochemical Systematics and Ecology, 2026)

Optimal combination of iron/magnesium salts and urea can promote the degradation rate of maize straw by catalyzing the rapid de-polymerization of lignin - Han Li; Yuan fang Zhou; Sen Zhao; Si hui Yan; Ding hua Jia; Yan ping Zhang; Xiang dong Yang; Juan Li (Biocatalysis and Agricultural Biotechnology, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

Does a positive culture correlate with the volume of synovial fluid inoculated into blood culture bottles for the diagnosis of periprosthetic joint infection? - Jia-Zheng Xu; Zhi-Sen Gao; Zhen Zhang; Ping Song; Wei Chai; Rui Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Identification and deformation monitoring of post-earthquake creep bodies after Ms 6.4 Yangbi earthquake - Ping Duan; Xuehao Yu; Haoran Liu; Juntang Nie; Zhike Zhang; Jia Li (Applied Geomatics, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Uncovering the Community Structure and Adaptive Characteristics of Soil Protists Across Natural, Semi‐Natural and Highly Degraded Habitats - Shi‐wei Feng; Xiaonan Wang; Ping Wen; Jing‐li Lu; Zhuo‐hui Wu; Xinzhu Yi; Wen‐sheng Shu; Jie‐Liang Liang; Pu Jia; Jin‐tian Li (Environmental Microbiology, 2026)
Protists are vital to soil ecological functions. However, their diversity and community patterns remain poorly characterised across habitats. This study investigated protists in 270 samples spanning five terrestrial ecosystems: natural (forest, grassland, desert), semi‐natural (farmland) and highly degraded (mine wasteland). The species richness of protists and the consumer functional group were highest in farmland and lowest in mine wasteland. We demonstrated that habitat type ( R partial Mantel = 0.291) exerted stronger effects on protistan communities than geographic distance ( R partial Mantel = 0.072). While α‐diversity drivers varied among habitats (e.g., total phosphorus (TP) was only positive in farmland and forest), β‐diversity was consistent and significantly correlated with mean annual temperature (MAT), mean annual precipitation (MAP), aridity index (AI) and moisture. We identified nine potential ecological groups of protists, reflecting their adaptive differentiation. To explore community assembly, a null model was conducted, revealing that stochastic processes dominated all habitats. Furthermore, co‐occurrence networks of protists, prokaryotes and fungi showed lower modularity and stability in mine wasteland compared with other habitats, indicating co‐occurrence patterns may be more specialised under resource limitation. Collectively, our results highlight the importance of habitat type in shaping protistan communities, suggesting that protists can be predictably regulated in degraded environments.

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Assessment of commercial NF membranes for selective separation of Mg2+/Li+ in simulated brines - Tian-tian Xue; Jian-wei Jia; Fan-xin Kong; Li-ping Yue; Guang-dong Sun; Jin-fu Chen (Journal of Water Process Engineering, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

A downscaling method for CMIP6 precipitation based on the Bayesian ridge spatiotemporal weighted regression model - Jiawen Yu; Ping Duan; Mingguo Wang; Wenbin Xie; Jia Li; Ying Xia (Climate Dynamics, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Predicting distribution characteristics of PM2.5 concentrations across China combining land use regression model and spatiotemporally weighted stacking machine learning algorithms - Wentao Wang; Ping Zhang; Yuanyuan Han; Fengqian Zhang; Yue Huang; Jinbao Liu; Ying Pan; Wenping Liu; Jian Chen; Mingyao Li; Yong Wang; Yefan Jia; et al. (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into high-pressure-induced structural and thermal changes of wheat starch in flour and dough systems - Yung-Jia Chan; Ping-Hsiu Huang; Xiao-Song Huang; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Hydrocolloids, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

Topographic primacy in rock glacier distribution revealed by GAMs and their water storage: Insights from a new polygonised inventory of the southeastern Tibetan Plateau - Ping Fu; Shuyang Xu; Tian Jia; Yang Zhan; Qian Zhang; Yingkui Li (CATENA, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Marine biomaterials for advanced food packaging: From sourcing to intelligent functional design and commercial prospects - Cheng Wang; Mengru Zhang; Tong Zhang; Haitao Du; Hongmin Xia; Renwei Guan; Fengdan Guo; Xinyi Li; Mingming Wang; Xiuwen Jia; Ping Wang (Trends in Food Science & Technology, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Diapause termination alters the m6A methylation profiles and regulates gene expression associated with early embryonic development in the silkworm (Bombyx mori) - Zhi-Hao Huang; Jia-Yue Yang; Cai-Ping Hou; Shi-Huo Liu; Bing Li; Jie Wang; Shou-jun Huang; Jia-Ping Xu (Journal of Insect Physiology, 2026)

Key structural characteristics enhancing digestion resistance in rice starch-sugarcane polyphenols complexes - Zhang Tong; Li Jia-Jiong; Fu Xiong; Wang Ping-Ping; Chen Hai-Ming; Chen Chun (Food Chemistry, 2026)

Hydrothermal stress influences the spatial distribution pattern of soil organic carbon and its stock in Xinjiang - Yunhao Li; Mingjie Shi; Ping'an Jiang; Jinzhi Gu; Jia Guo; Jiahao Zhao; Gongxin Wang; Yanmin Fan; Hongqi Wu (CATENA, 2026)

Cyflumetofen disrupts the blood-brain barrier and induces neurotoxicity in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

UAV-SfM coupled PBD simulation of graded rockfall fragmentation and air resistance: validation at Bijiashan, Chongqing - Jian Ping Pan; Lu Li; Wei Gao; Dan Huang; Jia Shu Liao (Bulletin of Engineering Geology and the Environment, 2026)

Long-term no-tillage altered microbial communities and reduced C degradation while facilitating denitrification in a semi-arid cropland - Yuzheng Zong; Weifeng Wang; Wanhong Jin; Yinglan Chen; Shaohui Jia; Qian Liu; Yali Cao; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Applied Soil Ecology, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Hydrogen distributions during thermal maturation of organic-rich sedimentary rocks: Generation potentials and influencing factors of hydrogen-bearing gases revealed by pyrolysis - Xiaodong Liu; Wanglu Jia; Qiang Wang; Jinbu Li; Jian Chen; Ping'an Peng (International Journal of Coal Geology, 2026)

Seismic performance of Chinese pavilion-type timber frame with forked column: Experimental tests - Zuoshuai Sun; Hongtai Zhang; Sicheng Li; Rui Zhang; Ping Xiang; Liang-jiu Jia (Engineering Structures, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Hydrological inundation legacy and seasonal variation jointly regulate soil respiration by shaping microbial community assembly in reservoir riparian zones - Kai Zhu; Fei Ye; Jiaqing Liu; Wenliu Zhang; Weitao Jia; Songlin Zhang; Jinlin Li; Shengjun Wu; Kang Dan; Yulin Wang; Ping Huang (CATENA, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Undescribed dihydro- β -agarofuran sesquiterpenoids from the roots of Tripterygium wilfordii - Ya-Lin Hu; Jia-Li Huang; Chong Wang; Wen-Jie Chen; Jing-Yi Huang; Yi-Ping Xie (Natural Product Research, 2026)

Polyprenylated xanthones with potential anti-inflammatory and anti-HIV effects from the stems and leaves of Cratoxylum cochinchinense (Lour.) Blume - Yong Zhang; You-Di Rao; Jing-Su Yu; Jia-Yi Hu; Wen-Hui Hu; Shu-Ri Li; Hui Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

A novel flexible branch-pinecone nanostructured UiO-66-MCA composite nanofiber membrane with bacteriostatic property for effective removal of salicylic acid - Yue Li; Jie Wang; Ping Lin; Shushu Jia; Lijuan Li; Yongxin Li; Ce Wang; Xiang Li (Water Research, 2026)

Long-term chemical fertilizer application enhances ammonia oxidizers-mediated soil carbon neutrality - Xueru Huang; Zhuo Zhang; Taoyi Ren; Song Li; Ping Zhu; Jingjing Ma; Zhongjun Jia; Jingkuan Wang; Marcela Hernández (Soil Biology and Biochemistry, 2026)

High-throughput screening identifies paullinic acid as an antiviral agent against Bombyx mori nucleopolyhedrovirus - Zhenwei Jia; Xiaoli Mo; Shidong Jiang; Li Sui; Yiling Zhang; Xueyang Wang; Jie Cheng; Ping Qian; Xudong Tang (Pesticide Biochemistry and Physiology, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Why does co-stewing shiitake mushrooms (Lentinula edodes) and beef synergistically enhance umami? An exploration from the perspective of umami peptides - Jiaxin Liu; Yujie Guo; Ping Yang; Hongbo Li; Haizhen Mo; Wei Jia; Zhenbing Liu; Chunhui Zhang (Food Research International, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Detecting and comparing extinction debts of amphibians in China under climate change - Yu-Xiao He; You-Hua Chen; Xiao-Qin Shi; Chao-Sheng Mu; Dan-Dan Yu; Jia-Qi Li; Hai-Gen Xu; Jian-Ping Jiang (Biological Conservation, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Innovative design of CXCR4 cyclic peptide via molecular docking for 99mTc-Labeled SPECT/CT imaging in melanoma - Xianrui Yin; Xin Wang; Chengwei Chen; Shenglan Jia; Wanhong Li; Yihong Wu; Xin Chen; Danling Feng; Wai Ping Cecilia Tsang; Zhihao Han; Yueqing Gu (Analytica Chimica Acta, 2026)

Synthetic derivatives of gibberellin A 3 with selective antiproliferative activity against human renal carcinoma 786-O cells - Jia-Hao Pang; Ke Wang; Xiao-Ping Peng; Gang Li (Natural Product Research, 2025)

Gut microbiota alterations after exposure to diesel exhaust particulate matter: Implications for hyperactivity and obesity - Hou Liu; Liuwen Chen; Ping Zhang; Yibin Jia; Jiaying Lu; Yajie Ji; Dan Li (Journal of Environmental Sciences, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Steering nitrogen and carbon dynamics for functional biochar and emission mitigation via co-pyrolysis of antibiotic-laden sludge and phytoremediation biomass - Zhibin Chen; Jingyong Liu; Ping Zhuang; Dajie Jia; Leyao Tao; Siqi Chen; Fatih Evrendilek; Tao Chen; Wenxiao Huang; Weixin Li (Chemical Engineering Journal, 2025)

Genome-wide analysis and functional validation of the GH1 gene family in cotton under salt stress - Liting Zhang; Junfeng Tang; Xiaoyu Tian; Hui Fang; Yifan Xu; Yiming Qian; Mengxue Jia; Ping Li; Baohua Wang; Zhimin Zhuang (Functional & Integrative Genomics, 2025)

Inhibitory Effect of TrxR Inhibitor Ag (Ⅰ) Schiff Base Complex Against Cervical Cancer Via ROS-mediated ASK1/MAPK Signaling and Autophagy - Jian-Jun Liu; Jia-Hua Zou; Bin Dong; Xue-Ping Lu; Li-Feng Chen; San-Mei Ma; Zhong Liu (Biological Trace Element Research, 2025)

Plastispheres as unique niches for promoting turnover of dissolved organic matter in aquatic environments - Yan-Jun Liu; Zheng-Hao Li; Yan-Yun Hu; Jia-Heng Zhao; Li Yuan; Guo-Ping Sheng (Water Research, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Overexpression of G protein-coupled receptors (GPCRs) contributing to lambda-cyhalothrin resistance in Cydia pomonella - Yu-Xi Liu; Chao Hu; Zi-Nan Xia; Yan Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Jia Li; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

Main controls on nitrogen cycling and Mo-U enrichment of the Middle Triassic Chang 7 Member in the Ordos Basin: Implications for redox and ultra-organic enrichment in a giant highly productive lake - Chuhan Zhao; Xiaodong Liu; Wanglu Jia; Wenzheng Zhang; Jian Chen; Jinbu Li; Ping'an Peng (Marine and Petroleum Geology, 2025)

Multi-omics profiling reveals the dynamic interplay between processing-induced phytochemical transformation and antioxidant bioactivity in ‘Huangkui’ tea (Camellia sinensis) - Zi Wang; Jia-Ping Ke; Gan Chen; Linxin Long; Liang Zhang; Yeyun Li; Zhougao Shen (Food Chemistry, 2025)

Flavoromic analysis of dynamic changes and metabolic pathways of flavor compounds in Shai vinegar across aging stages and types - Haibin Yuan; Tianyang Wang; Yang Liu; Hongfeng Jia; Qi Jia; Yanlin Li; Huachang Wu; Ping Dong (Food Chemistry, 2025)

Elucidating flavor compounds in Chinese steamed bread via glutinous rice wine-fermented dough technique: A triangulated analysis combining electronic tongue, SPME-GC-MS, and quantitative descriptive analysis - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Bioscience, 2025)

Gut microbiota modulation by structurally diverse foodborne polysaccharides: In vitro fermentation and prebiotic activity evaluation - Lu Wang; Jia-hao Fan; Yao Yang; Hong-wei Qiu; He-he Li; Wen-yi Kang; Guang-ping Lv (Food Bioscience, 2025)

Network-based investigation of norfloxacin-induced nasal immune-related inflammatory responses in carp (Cyprinus carpio) and its cross-species implications for olfactory immune disturbance - Jia-Ming Zhang; Ping Li; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Zhi-Hua Li (Fish & Shellfish Immunology, 2025)

High-severity fire reduces soil erosion resistance: A study based on 4-year field monitoring data in dry-warm valley in Southwest China - Xiaosong Qin; Yi Wang; Longxi Cao; Ping Ren; Wei He; Yongkang Li; Dongdong Hou; Yufan Wang; Jia Xu (CATENA, 2025)

Integrating methane conversion with multi-pathway nitrogen removal for wastewater in membrane-enabled stratified biofilm: System development and microbial dynamics - Chun-Yan Yuan; Yu-Xia; Jia-Hao Huo; Cai-Long Nie; Ke-Xin Zhang; Liang-Feng; Xiao-Li Su; Zi Song; Gen-Ping Yi; Fei-Yun Sun (Bioresource Technology, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Black rice stepwise fermentation enhances yogurt gel quality: Solidification rate, texture, LAB distribution and viability persistence - Jiarui Zeng; Zhiming Wang; Guang Liu; Xuchao Jia; Pengfei Zhou; Ping Li; Zhihao Zhao; Yan Zhang; Xiaojun Tang; Dong Liu; Yuanyuan Deng; Mingwei Zhang (Food Chemistry, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Corrigendum to ‘Quantification of free and adsorbed fluid content in shale oil reservoirs: Insights from preserved cores and different methods’ [Mar. Petrol. Geol. 177 (2025) 107400] - Hongrui Zhang; Jinbu Li; Wanglu Jia; Min Wang; Ping'an Peng (Marine and Petroleum Geology, 2025)

Ice ball size and temperature change during cryoablation in a lard and an ethiodized-oil tissue phantom - Nai-Wen Chang; Shu-Huei Shen; Chien-An Liu; Felix Antony Halim; Jia-An Hong; Chih-Chien Li; Ping-Lang Yen (Cryobiology, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Ratiometric photoelectrochemical aptasensor for ultrasensitive kanamycin detection based on superior photoactive high-entropy sulfide nanosheets coupling with dual-atom nanozyme inducing polarity switch - Jia-Lin Li; Li-Ping Mei; Ai-Jun Wang; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Polyethylene biodegradation by gut microbiota of Lasioderma serricorne: Isolation, identification, and mechanistic insights - Ming-Fei Wu; Pan-Pan Jia; Ling He; Li-Ping Ma; Yan Li; Lan-Chen Zhang; Dong-Mei Xie; Xiao-Bing Li; Tian-Nv Wang; De-Sheng Pei (Chemical Engineering Journal, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Comparative Efficiency of High-Throughput Magnetic Bead Method and Polyethylene Glycol Precipitation for Viral Concentration in Sewage - Jingyi Jiang; Li Gong; Ping Yao; Jian Xu; Xujian Mao; Jia Chen; Jinyi Jiang; Xiaoqiang Li; Qiong Li; Fengming Wang (Food and Environmental Virology, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Identifying the determinants of natural, anthropogenic factors and precursors on PM1 pollution in urban agglomerations in China: Insights from optimal parameter-based geographic detector and robust geographic weighted regression models - Ping Zhang; Yong Wang; Wenjie Ma; Mingyao Li; Yonghua Zhao; Wentao Wang; Yefan Jia; Jinghao Fan; Lufang Kong; Kang Hou; Yuanyuan Han (Environmental Research, 2025)

Metabolome and Genome Analysis of a Novel Endophytic Fungus Aureobasidium pullulans KB3: Discovery of Polyketones and Polyketone Biosynthesis Pathway - Shuai Wang; Jia-Nuo He; Ying-Jie Wang; Wen-Ya Zhao; Qing-Xia Yang; Ya-Na Wang; Yang Zhang; Li-Ping Zhang; Hong-Wei Liu (Biochemical Genetics, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

A leader-follower contrastive learning framework for imbalanced multimodal remote sensing image classification - Jia Li; Lin Zhao; Ping Tan; Minhui Zhao; Guoyun Zhang; Xinping Li (International Journal of Remote Sensing, 2025)

Effect of wave height on seismic fragility of subsea tunnels in sandy seabed - Ling-Yu Xu; Ju-Ping Xi; Jia-Wei Jiang; Fei Cai; Yong-Yi Li; Guo-Xing Chen (Ocean Engineering, 2025)

Quantification of free and adsorbed fluid content in shale oil reservoirs: Insights from preserved cores and different methods - Hongrui Zhang; Jinbu Li; Wanglu Jia; Min Wang; Ping'an Peng (Marine and Petroleum Geology, 2025)

Geochemical characteristics of light hydrocarbons generated in thermochemical sulfate reduction: Results from three series of simulation experiments - Zhenyu Sun; Jian Chen; Wanglu Jia; Qiang Wang; Jie Xu; Xin Li; Jianghu Yang; Ping'an Peng (Marine and Petroleum Geology, 2025)

Bioremediation potential of sulfadiazine-degrading bacteria: Impacts on ryegrass growth and soil functionality - Minghao Yin; Ping Li; Chengzhuang Chen; Ruolan Jia; Banghua Xia; Yiwei Liu; Aiqiu Liu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Investigating the fine structures of ginkgo starch during kernel development and their correlations with thermal properties - Yan Lu; Lian Zhou; Cai-Yun Zhang; Yan Qi; Xiao-Min Zhang; Zhang Pan; Hong-Jia Zhang; Yu-Ping Ling; Qing Liu; Chang-Quan Zhang; Li Wang (Food Chemistry, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Dynamic changes in DNA methylation and correlated expressing genes during somatic embryogenesis in Hevea brasiliensis - Ling Li; Jia Miao; Jin Liu; Ming-Chun Gui; Min Tang; Hai Tian; Wan-Yuan Shi; Guo-Ping Liang; Xiao-Long Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Investigating the Potential Therapeutic Targeting of the JAK-STAT Pathway in Cerebrovascular Diseases: Opportunities and Challenges - Jia-Wei Wu; Bing-Xin Wang; Li-Ping Shen; Yong-Lin Chen; Zhi-Yong Du; Shi-Qing Du; Xiao-Jie Lu; Xu-Dong Zhao (Molecular Neurobiology, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Emissions characteristics of polycyclic aromatic hydrocarbons, water-soluble heavy metals, and oxidative potential from indoor non-energy combustion sources - Si-Min Zhao; Wen-Xin Liu; Qi-Yu Miao; Jia-Min Li; Lu-Min Sun; Shui-Ping Wu (Environmental Science and Pollution Research, 2025)

Early Eocene Metasequoia and Taxodium (Cupressaceae) from Lingbao, Henan Province and their implication for a perhumid climate in central China - Ping Liu; Hui Jia; Li Xu; Yu Li; Ming-Yue Luo; Tian-Qi Dong; Jiao Huang; Cheng Quan (Palaeoworld, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Effects of early-life F-53B exposure on thyroid function in juvenile rats: The role of the cAMP signaling pathway - Shen-Pan Li; Wen-Hui Zhao; Jing Zhang; Wen-Ting Jiang; Jia-Yi Zhu; Yi-Xin Luo; Ping Xiang; Michael Bloom; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Livistona chinensis leaves bioorganic frame derived porous carbon material containing Fe-Nx active site as oxygen reduction electrocatalyst for zinc-air batteries - Kun Fang; Chen Ling; Yan-Fang Yao; Hao Zhang; Jia-Jie Wu; Li-Ping Si; Hai-Yang Liu (Journal of Environmental Chemical Engineering, 2025)

Impact of fermentation duration in fermented glutinous rice wine dough procedure on the staling of Chinese steamed bread - Jia-Xuan Shang; Jia-Xuan Li; Feng-Ping Qin; Yi-Peng Bai; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Toxic effects of emerging pollutants on mucosal organs of teleost fish: A review focusing on mucosal microbiota, physical barrier and immune barrier - Jia-Ming Zhang; Ping Li; Cheng-Zhuang Chen; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

Multifunctional Sr/Zn-doped TiO2 micro/nanoporous coating enhances osseointegration by modulating signaling crosstalk of bone-related cells - Tian-Xia Zheng; Nuo-Ya Yang; Jiu-Peng Deng; Wei Dong; Li-Fang Feng; Yuanyuan-Ding; Jin-Ping Yang; Xin-Jia Cai; Yan Liu; Meng-Chun Qi (Chemical Engineering Journal, 2025)

A Golden2-like transcription factor regulates Brassica napus seed vigor after artificial aging - Xiaoke Ping; Mei Yan; Jia Wang; Qianjun Ye; Taiyuan Zhang; Xiaojie Hu; Sheng Chen; Jiana Li; Liezhao Liu (Theoretical and Applied Genetics, 2025)

Moisture–Microbial Interaction Amplifies N 2 O Emission Hot Moments Under Deepened Snow in Grasslands - Jie Luo; Yong Peng; Zhou Jia; Yuntao Wu; Yuxuan Gao; Nairsag Jalaid; Xingming Zhang; Heng Ge; Bowen Qing; Hongyi Chen; Yanxin Zhan; Ping Li; et al. (Global Change Biology, 2025)
Freeze–thaw‐induced N 2 O pulses could account for nearly half of annual N 2 O fluxes in cold climates, but their episodic nature, sensitivity to snow cover dynamics, and the challenges of cold‐season monitoring complicate their accurate estimation and representation in global models. To address these challenges, we combined in situ automated high‐frequency flux measurements with cross‐ecoregion soil core incubations to investigate the mechanisms driving freeze–thaw‐induced N 2 O emissions. We found that deepened snow significantly amplified freeze–thaw N 2 O pulses, with these ~50‐day episodes contributing over 50% of annual fluxes. Additionally, freeze–thaw‐induced N 2 O pulses exhibited significant spatial heterogeneity, ranging from 3.4 to 1184.1 μg N m −2 h −1 depending on site conditions. Despite significant spatiotemporal variation, our results indicated that 68%–86% of this variation can be explained by shifts in controlling factors: from water‐filled pore space (WFPS), which drove anaerobic conditions, to microbial constraints as snow depth increases. Below 43% WFPS, soil moisture was the overwhelmingly dominant driver of emissions; between 43% and 66% WFPS, moisture and microbial attributes (including denitrifying gene abundance, nitrogen enzyme kinetics, and microbial biomass) jointly triggered N 2 O emissions pulses; above 66% WFPS, microbial attributes, particularly nitrogen enzyme kinetics, prevailed. These findings suggested that maintaining higher soil moisture served as a trigger for activating microbial activity, particularly enhancing nitrogen cycling. Furthermore, we showed that hotspots of freeze–thaw‐induced N 2 O emissions were linked to high root production and microbial activity in cold and humid grasslands. Overall, our study highlighted the hierarchical control of WFPS and microbial processes in driving freeze–thaw‐induced N 2 O emission pulses. The easily measurable WFPS and microbial attributes predictable from plant and soil properties could forecast the magnitude and spatial distribution of N 2 O emission “hot moments” under changing climate. Integrating these hot moments, particularly the dynamics of WFPS, into process‐based models could refine N 2 O emission modeling and enhance the accuracy of global N 2 O budget prediction.

Deepened snow promotes temporal stability of semi‐arid grasslands via improving water acquisition‐and‐use strategies - Ping Li; Zhou Jia; Yuntao Wu; Pengfei Chang; Nairsag Jalaid; Lulu Guo; Shengnan Pan; Shaopeng Wang; Lin Jiang; Shuijin Hu; Lingli Liu (Ecology, 2025)
Precipitation fluctuations strongly influence biomass production and its stability of terrestrial ecosystems. However, our understanding of the extent to which plant communities adjust their water‐use strategies in response to non‐growing season precipitation variations remains limited. Our 5‐year snow manipulation experiment in a semi‐arid grassland, complemented with paired stable isotope measurements of δ 18 O and δ 13 C for all species within the community, demonstrated that the impact of snowmelt on plant physiological activities extended into the peak growing season. Deepened snow enhanced ecosystem water use efficiency (WUE), biomass production, and its temporal stability. We further examined whether the observed increase in biomass stability was associated with the functional diversity of plant water‐use strategies. Plant cellulose Δ 18 O cell analysis revealed that both community‐weighted mean and functional dispersion of stomatal conductance were positively associated with biomass production and its stability. The δ 13 C results further indicated that even with increased stomatal conductance, grasses were able to maintain their high intrinsic WUE by increasing photosynthesis more than transpiration. This resulted in higher biomass and greater dominance of high‐WUE functional groups under deepened snow. In addition, we also found that deepened snow increased root biomass, particularly in the 0‐ to 5‐cm and 20‐ to 40‐cm soil layers. This increase in root biomass enhanced the uptake of snowmelt from both surface and deep soil layers, further contributing to community stability. Overall, our study demonstrates that plant communities can optimize water acquisition and utilization, thereby enhancing the stability of biomass production through coordinated changes in plant physiology, species reordering, and root distribution under altered snow regimes.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Dry season dominance of salinity’s impact on hydrogen isotope fractionation in Aegiceras corniculatum mangrove lipids - Yao-Ping Wang; Zhiguang Song; Jia Xia; Zhao-Wen Zhan; Alex L. Sessions; Shaelyn N. Silverman; Yuan Gao; Guopeng Li; Ding He (Geochimica et Cosmochimica Acta, 2025)

Advancing lactic acid Fermentation: Effects of micro aeration and herbal waste on red clover bioconversion - Chaosheng Liao; Mingjie Zhang; Pan Wang; Xiaolong Tang; Minghong You; Changbing Zhang; Guofu Jia; Wenlong Gou; Ning Mao; Yixiao Xie; Chao Chen; Shiqie Bai; et al. (Chemical Engineering Journal, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Regeneration of in vitro plants through direct and indirect organogenesis from Dracocephalum rupestre leaf explants - Jia li Wang; Kang jie Yue; Hui xin Liu; Xu ping Tian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Changes in source contributions to the oxidative potential of PM2.5 in urban Xiamen, China - Jia-Min Li; Si-Min Zhao; Qi-Yu Miao; Shui-Ping Wu; Jie Zhang; James J. Schwab (Journal of Environmental Sciences, 2025)

Proteomics analysis reveals the antagonistic interaction between high CO2 and warming in the adaptation of the marine diatom Thalassiosira weissflogii in future oceans - Jiamin Lin; Jingyao Li; Xiao Liang; Hao Zhang; Baoyi Peng; Leyao Xu; Yuan Jia; Bin Huang; Fangzhou Liu; Peixuan Liu; Mengcheng Ye; Fenghuang Wu; et al. (Environmental Pollution, 2025)

Landslide displacement prediction using time series InSAR with combined LSTM and TCN: application to the Xiao Andong landslide, Yunnan Province, China - Jia Li; Chengpeng Fan; Kang Zhao; Zhike Zhang; Ping Duan (Natural Hazards, 2025)
Research on landslide displacement prediction based on interferometric synthetic aperture radar (InSAR) deformation data involves two main issues. First, InSAR can provide only one-dimensional deformation data along the satellite’s line of sight (LOS), which cannot truly reflect the deformation of the landslide body in the downward direction along the slope. Second, the use of a single prediction model does not adequately account for both long-term and local changes in landslide displacement, affecting the accuracy of the predictions. To address this, in this study, Long Short-Term Memory networks (LSTM) and temporal convolutional network (TCN) models are combined to construct a method (LSTM-TCN) of landslide displacement prediction. This method can consider the long-term and localized changes in landslide displacement. The method is first based on InSAR technology to obtain surface deformation. The deformation of the landslide is subsequently computed in the downward direction along the slope to obtain the landslide displacement time series data. Next, the LSTM-TCN is used for landslide displacement prediction. Finally, the mean absolute error (MAE), root mean square error (RMSE) and coefficient of determination (R 2 ) are used to evaluate the performance of the model. The experiment is conducted on the Xiao Andong landslide in Anshi village, Fengqing County, Lincang City, Yunnan Province, China. The LSTM-TCN model achieves an R 2 of 0.75, an RMSE of 0.43 cm, and an MAE of 0.36 cm. Compared with the individual LSTM and TCN models, the LSTM-TCN model exhibits the highest prediction accuracy and the smallest prediction error, which is closer to the true result that in the other models. These results demonstrate that the combined LSTM-TCN model effectively captures the complex features and long-term trends in landslide displacement data, significantly enhancing the accuracy of predictions.

Transparent geological exploration for intelligent and safe open-pit mining based on ambient noise seismic imaging - Ping-Feng Li; Qiang-Qiang Zheng; Ying Xu; Di Wei; Jia-wei Qian; Bao-Ji Yang (Applied Geophysics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Metabolomics-based mechanistic insights into antioxidant enhancement in mango juice fermented by various lactic acid bacteria - Shuai Liu; Yu-Jia Peng; Wei-Wei He; Xiao-Xiao Song; Yu-Xin He; Xiao-Yi Hu; Shui-Gen Bian; Yu-Hao Li; Jun-Yi Yin; Shao-Ping Nie; Ming-Yong Xie (Food Chemistry, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Comparative chloroplast genomic analysis of an important horticultural plant, Dendrobium sulcatum (Orchidaceae) and phylogenetic position in Dendrobium - Feng-Ping Zhang; Jia-Jun Deng; Ying Guo; Li-Jun Han; Zi-Li Yin (Horticulture, Environment, and Biotechnology, 2025)

Influence of topography on the fragmentation and mobility of landslides - Zhaodong Li; Jian Guo; Tonglu Li; Ping Li; Xuetong Ma; Mengmeng Zhang; Enxian Jia; Pingping Xu (Bulletin of Engineering Geology and the Environment, 2025)

Conventional and biodegradable microplastics affected arsenic mobility and methylation in paddy soils through distinct chemical-microbial pathways - Hai-Qian Li; Jin-Peng Lv; Yue-Hui Jia; Jie Liu; Qiong Liang; Jian Zhou; Ai-Zhen Yang; Teng Yan; Yu-Ping Yang; Gui-Lan Duan (Journal of Hazardous Materials, 2025)

Flooding increases plant-derived carbon accumulation in soils of aquatic-terrestrial ecotone - Yiguo Ran; Ziqiang Mao; Hanzhong Jia; Xianjing He; Shaopan Xia; Fei Ye; Chamindra L. Vithana; Siyue Li; Shengjun Wu; Ping Huang (Journal of Environmental Management, 2025)

Structural characterization and proteomic profiling of oviposition secretions across three rice planthopper species - Jia-Bao Lu; Peng-Peng Ren; Ying Tian; Yan-Yan Yang; Qing-Kai Feng; Xiao-Ya Zhang; Fang He; Hai-Jian Huang; Jian-Ping Chen; Jun-Min Li; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2025)

Petrogenesis of the unbrecciated pigeonite cumulate eucrite Northwest Africa 8326: Bridging the gap between eucrites and diogenites - Xiao-Wen Liu; Ai-Cheng Zhang; Li-Hui Chen; Lang Zhang; Xiao-Jun Wang; Jia Liu; Li-Ping Qin; Yu Liu; Qiu-Li Li; Xiao-Xiao Ling (Geochimica et Cosmochimica Acta, 2025)

Study on the condensate gas phase behavior in Nano-porous media - Ping Wang; Yuepeng Jia; Junjie Zhong; Wensong Huang; Wei Ding; Peng Lian; Xiangwen Kong; Li Liu; Zibin Zhao (Fuel, 2025)

Developed metabolomics approach reveals the non-volatile color-contributing metabolites during Keemun congou black tea processing - Mingchun Wen; Wei Hu; Lu Li; Piaopiao Long; Zisheng Han; Jia-Ping Ke; Zhiyang Deng; Mengting Zhu; Liang Zhang (Food Chemistry, 2025)

Investigating the application of multiple-stage fermented glutinous rice procedure in dough preparation for Chinese steamed bread - Jia-Xuan Li; Jia-Xuan Shang; Feng-Ping Qin; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

Efficient Cu recovery from wastewater via Cu(III)-triggered Cu-organics decomplexation using hierarchical porous carbon as particle electrode in a three-dimensional electrochemical reactor - Pu-Can Guo; Wang-Xiao Jia; Keng-Qiang Zhong; Li Yuan; Guo-Ping Sheng (Chemical Engineering Journal, 2025)

Biomimetic superparamagnetic gelatin/chitosan asymmetric fibrous membrane for accelerating wound healing under static magnetic field - Jingxi Wang; Kun Li; Yunxue Jia; Tianran Song; Junwei Xu; Xuemei Sun; Meili Liu; Ping Li; Yubo Fan (Carbohydrate Polymers, 2025)

The complex interplay of flooding intensity and land use on soil microbial communities in riparian zones: Insights for ecological restoration - Kai Zhu; Fei Ye; Yu Mei; Weitao Jia; Xiai Zhu; Shuzhen Li; Shengjun Wu; Songlin Zhang; Ping Huang (CATENA, 2025)

Sevoflurane postconditioning mitigates neuronal hypoxic-ischemic injury via regulating reactive astrocytic STAT3 protein modification - Yufei Jia; Yanhong Song; Hang Xue; Xingyue Li; Yinong Zhang; Shiyue Fan; Xu Yang; Zixuan Ding; Yue Qiu; Ziyi Wu; Ping Zhao (Chemico-Biological Interactions, 2025)

Harnessing diurnal dynamics: Understanding the influence of light–dark cycle on algal-bacterial symbiotic system under aniline stress - Qi He; Qian Zhang; Meng Li; Jing He; Bing Lin; Nan-Ping Wu; Jia-Jing Chen; Xun-Hao Liu; Xiao-Qian Dong (Bioresource Technology, 2025)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Application of botulinum toxin A in tissue repair and regeneration - Xuan-Zhu Guo; Ya-Nan Niu; Xuan Zhou; Qiao Wei; Meng Li; Jia-Ning Xia; Yu-Qi Cui; Chao-Xin Chai; Yi-Ming Wang; Li-Ping Chen (Toxicon, 2024)

Miocene evolution of vegetation, climate, and elevation in the Wulan Basin of northeast Tibetan Plateau based on a CRACLE analysis of palynological assemblages - Xiao-Mei Li; Jia-Yi Chen; Zhen-Dong Cao; Li-Ming Liu; Si-Hang Zhang; Yun-Zhe Zhang; Li-Jie Wei; San-Ping Xie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Influencing factors of hydrogen isotopic fractionation of light hydrocarbons during evaporation and implications - Wenna Liu; Wanglu Jia; Qiang Wang; Jian Chen; Jinbu Li; Ping’an Peng (Organic Geochemistry, 2024)

Tectonic-climate-wildfire coupling during the Miocene in the northeastern Qinghai-Tibetan Plateau - Li-Ming Liu; Zhen-Dong Cao; Xiao-Mei Li; Si-Hang Zhang; Yun-Zhe Zhang; Jia-Yi Chen; De-Fei Yan; San-Ping Xie (Journal of Asian Earth Sciences, 2024)

Integration of automatic discontinuity identification and multi-scale hierarchical modeling for stability analysis of highly-jointed rock slopes - Ya-ping Wang; Jia-wen Zhou; Jun-lin Chen; Yu-chuan Yang; Fei Ye; Hai-bo Li (International Journal of Rock Mechanics and Mining Sciences, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

Unlocking superior preservation: The synergy of lignin and zeolite in chitosan-based composite films for perishable foods - Zhan-Chao Li; Xi Chen; Jia-Li Zhang; Xiao-Ping Gao; Yan-Xia An; Li-Jie Wu; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Packaging and Shelf Life, 2024)

Variations and driving factors for concentrations and carbon isotopes of dissolved CO2 in lake water across different Chinese lakes - Hu Liu; Jia Liu; Huanye Wang; Zhonghui Liu; Xiangzhong Li; Ping Zhang; Weiguo Liu; Shangbin Xiao (Environmental Research, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Polymorphisms of PRKAA1 and FABP4 genes and their association with feed efficiency in Hu sheep - Mengru Pu; Deyin Zhang; Liming Zhao; Dan Xu; Zongwu Ma; Kunchao Han; Lijuan He; Chengqi Yan; Qi Zhang; Lianjun Feng; Ziyue Xiao; Lei Gao; et al. (Small Ruminant Research, 2024)

Conjugation-regulated lateral and stereoelectronic effects in single-molecule junctions - Xiao Wei; Xuanhao Cao; Jie Hao; Xinyue Chang; Ping Duan; Li Cheng; Keqiu Chen; Jinying Wang; Chuancheng Jia; Xuefeng Guo (Chemical Engineering Journal, 2024)

Aberrant Enhanced NLRP3 Inflammasomes and Cell Pyroptosis in the Brains of Prion-Infected Rodent Models Are Largely Associated with the Proliferative Astrocytes - Dong-Hua Zhou; Xiao-Xi Jia; Yue-Zhang Wu; Wei-Wei Zhang; Yuan Wang; Dong-Lin Liang; Li-Ping Gao; Kang Xiao; Cao Chen; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Epidemiology and genetic diversity of bocavirus in wild rodents in urban areas of Guangzhou, Southern China - Xin-Yan Yao; Chao-Xiang Jia; Chang-Le Li; He-Ping Li; Kai Zhong; Jian-Wei Shao; Yue-Ying Wang (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Efficient and low-cost Ni-NiO/Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide - Liang-Liang Zhang; Xiao-Min Duan; Kai-Xuan Yang; Yu-Bo Xu; Jia-Ping Lu; Wan-Xi Li; Bo-Qiong Li; Cai-Long Xue; Ya-Jie Liu (Chemical Engineering Journal, 2024)

Sensitivity of cloud microphysics to aerosol is highly associated with cloud water content: Implications for indirect radiative forcing - Yuan Wang; Hailing Jia; Ping Zhang; Fang Fang; Jiayi Li; Lei Zhu; Yang Wang; Tianshu Wang; Jiming Li (Atmospheric Research, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Evaluation of combined disinfection methods of infectious myonecrosis virus (IMNV) in seawater using Pacific white shrimp (Penaeus vannamei) - Mingshu Yang; Bensen Wang; Ruidong Xu; Ping Li; Jitao Xia; Tianchang Jia; Wenqiang Li; Yuying Zhang; Qingli Zhang (Aquaculture, 2024)

Environmental microbes alleviate antibiotic disturbance on plant endophytes in aquatic microcosms: Prospects for conferring fitness benefits - Yi Hu; Fan-Li Meng; Jia-Heng Zhao; Guo-Ping Sheng (Water Research, 2024)

Avermectin induced vascular damage in zebrafish larvae: association with mitochondria-mediated apoptosis and VEGF/Notch signaling pathway - Wei-Guo Wang; Xu-Feng Jiang; Cheng Zhang; Xiu-Ping Zhan; Jia-Gao Cheng; Li-Ming Tao; Wen-Ping Xu; Zhong Li; Yang Zhang (Journal of Hazardous Materials, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

Effects of sand substrate removal on the intestinal antioxidant and metabolism in Marsupenaeus japonicus - Kuangcheng Zhao; Shaoting Jia; Junxia Wang; Xueqiong Bian; Shibo Chen; Jitao Li; Ping Liu; Jian Li; Yuefeng Cai; Xianyun Ren (Fish & Shellfish Immunology, 2024)

Histopathology and transcriptome profiling reveal features of immune responses in gills and intestine induced by Spring viremia of carp virus - Ping Ouyang; Qiunan Li; Shuya Liu; Yankai Li; Shuhan Li; Yongheng Zhou; Peng jia; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Moss differentiating the fluxes and sources of nitrogen deposition between 1984 and 2021 in a mountain area of Northern China - Jia-Yi Li; Yu-Ping Dong; Yang Wang; Tong-Yue Deng; Zun-Tian Zhao (Chemosphere, 2024)

Salinity decreases methane concentrations in Chinese lakes - Hu Liu; Shangbin Xiao; Weiguo Liu; Huanye Wang; Zhonghui Liu; Xiangzhong Li; Ping Zhang; Jia Liu (Science of The Total Environment, 2024)

The complete genome sequence of the planctomycetotal bacterium Bremerella sp. P1 with abundant genes involved in polysaccharide degradation - Jia-Xuan Wang; Jing Wang; Ji-Qing Liu; Jian Li; Wen-Xin Jiang; Fei Xu; Ping-Yi Li; Qi-Long Qin; Xiu-Lan Chen; Xi-Ying Zhang (Marine Genomics, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Deciphering the influence of salinity stress on the biological aniline degradation system: Pollutants degradation performance and microbial response - Qi He; Bin Tan; Meng Li; Junhao Su; Bing Lin; Nan-ping Wu; Hao-nan Shen; Jia-jing Chen; Qian Zhang (Environmental Research, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Formation of secondary organic aerosols from Cl-initiated oxidation of anisole: Rapid release of ultrafine particles and organic chlorides - Fashuai Pan; Jiaoyang Ma; Qianqian Yan; Gaosheng Zhao; Bin Jia; Li Xu; Ping Cheng (Atmospheric Environment, 2024)

Biosafety assessments of hexafluoropropylene trimer derivative as a fluorinated cooling fluid for electronics - Yi-Tong Zhou; Pei-Jie Zhang; Shu-Ping Wang; Chang-Hao Li; Jia-Qing Zhang; Wei-Xin Zhang; Yuan-Di Zhao; Yuan-Cheng Cao; Jin-Xuan Fan (Toxicological Research, 2024)

How extreme hydrological events correspond to climate extremes in the context of global warming: A case study in the Luanhe River Basin of North China - Ge Gao; Jianzhu Li; Ping Feng; Jia Liu; Yicheng Wang (International Journal of Climatology, 2024)
The consensus on climate warming is well‐established, and extreme values inherently encapsulate more information than averages. Against the backdrop of frequent extreme climate events, studying extreme values holds profound significance. This study aims to reveal the characteristics of extreme climate events and their role in triggering extreme hydrological events in the typical North China basin, that is, the Luanhe River Basin. Trends of 25 extreme climate indices during 1960–2018 are analysed using the Sen's slope and MK significance test to study the changing characteristics of extreme climate. Characteristics of extreme flood and dry events are examined, encompassing trend analyses at different time scales (seasonal, interannual, decadal) and concentration analysis. Finally, and most significantly, correlation analysis is conducted on extreme climate indices and features of extreme hydrological events, followed by principal component analysis of extreme climate indices, to precisely quantify the impact of extreme climate on the occurrence of extreme hydrological events. The results indicate a warming trend in extreme temperature indices, with a more significant rise in minimum temperatures compared to maximum temperatures. There is a significant decrease in precipitation, but precipitation at higher magnitudes is less affected by the overall reduction in total precipitation. Extreme dry events have markedly increased, particularly concentrated in winter with delayed occurrences, primarily induced by extreme temperature events, that is, warming effects. Conversely, extreme flood events have significantly decreased, mainly concentrated in summer and early autumn, predominantly caused by extreme precipitation and extreme high‐temperature events. The climate and hydrological conditions in the study area have become more extreme and complex. Severe river droughts may occur more frequently in winter, while extreme flooding may happen in summer. Therefore, it is necessary to pay more attention to these developments.

The sesquiterpenes with the COVID-19 M pro inhibitory activity from the Carpesium abrotanoides L. - Yu-Wen Fan; Zhuo-Yi Ao; Wei-Jie Zhang; Jia-Yan Chen; Xin Lian; Yong- Chen Pan; Li-Ping Chen; Jie-Wei Wu; Jie Yuan (Natural Product Research, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Developing novel ensemble models for predicting soil hydraulic properties in China’s arid region - Liantao Niu; Xiaoxu Jia; Xiangdong Li; Chunlei Zhao; Lidong Ren; Wei Hu; Ping Zhu; Danfeng Li; Baoqing Zhang; Ming'an Shao (Journal of Hydrology, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

Dynamic energy evolution and fragmentation characteristics of damaged rock under impact compression loading - Qiang-Qiang Zheng; Jia-Wei Qian; Ping-Feng Li; Zhi-Qiang Yin; Huan-Ting Zhao (Applied Geophysics, 2024)

Performance on adsorption of toluene by ionic liquid-modified AC in high-humidity exhaust gas - Ji-feng Guo; Zhao-li Ping; Nan Liu; Xin Zhang; Jia-lin Lv; Yan-yan Yao; Jia-jun Hu; Wen-juan Wang; Ji-xiang Li (Environmental Science and Pollution Research, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Spatio-temporal patterns of intense tropical cyclones in the Western North Pacific over the past 1600 years - Liang Zhou; Rumeng Hao; Mingchen Li; Yan Su; Shu Gao; Yang Yang; Zhixiong Shen; Jianjun Jia; Ya Ping Wang (Marine Geology, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

High efficiency removal of NO using waste calcium carbide slag by facile KOH modification - Fang Wang; Hui Li; Jiyun Gao; Na Geng; Enzhu Jiang; Futing Xia; Mingwu Xiang; Lijuan Jia; Ping Ning (Journal of Environmental Sciences, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

Simultaneous and on-line detection of organic and heavy metal components in water using a novel nebulization-assisted injection plasma ionization triple quadruple mass spectrometry instrument - Gaosheng Zhao; Maolin Yang; Tingting Zhang; Bin Jia; Li Xu; Ping Cheng (Analytica Chimica Acta, 2024)

Deep degradation of atrazine in water using co-immobilized laccase-1-hydroxybenzotriazole-Pd as composite biocatalyst - Juan Jia; Ping Xue; Lan Ma; Peng Li; Chongrui Xu (Journal of Hazardous Materials, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Miocene Equisetum tubers from the Wulan Basin, Northeast Qinghai-Tibetan Plateau and their paleoecological significance - Zhen-Dong Cao; Peng Zhang; Si-Hang Zhang; Yi-Hong Yang; Jia-Yi Chen; Li-Ming Liu; Xiang-Chuan Li; San-Ping Xie (Palaeoworld, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Evolution of suspended sediment concentration profiles in the partially and periodically stratified Changjiang Estuary during dry season - Zhanhai Li; Jianjun Jia; Fan Zhang; Ya Ping Wang; Shu Gao (Estuarine, Coastal and Shelf Science, 2024)

Dynamic, synergistic, and optimal emissions and kinetics of volatiles during co-pyrolysis of soil remediation plants with kaolin/modified kaolin - Zhibin Chen; Weijie Li; Shengzheng Huang; Ping Zhuang; Dajie Jia; Fatih Evrendilek; Sheng Zhong; Yoshihiko Ninomiya; Zuoyi Yang; Yao He; Wuming Xie; Jingyong Liu; et al. (Chemical Engineering Journal, 2024)

Glass-cobalt Janus shell hollow microspheres: Shell structure dependence of mechanical strength and electromagnetic property - Qianqian Jia; Man Li; Zhenguo An; Ping Wang; Jingjie Zhang (Chemical Engineering Journal, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

Size-segregated characteristics of water-soluble oxidative potential in urban Xiamen: Potential driving factors and implications for human health - Jia-Min Li; Si-Min Zhao; Shui-Ping Wu; Bing-Qi Jiang; Yi-Jing Liu; Jie Zhang; James J. Schwab (Science of The Total Environment, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Micro(nano)plastics in marine medaka: Entry pathways and cardiotoxicity with triphenyltin - Ling Liu; Ren-Yan Du; Ruo-Lan Jia; Jin-Xin Wang; Cheng-Zhuang Chen; Ping Li; Ling-Ming Kong; Zhi-Hua Li (Environmental Pollution, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

Expansion of YALIcloneHR toolkit for Yarrowia lipolytica combined with Golden Gate and CRISPR technology - Qi Shen; Fang Yan; Ya-Wen Li; Jian Wang; Jia Ji; Wen-Xin Yan; Dan-Chen He; Ping Song; Tian-Qiong Shi (Biotechnology Letters, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

The clinical trajectory of peripheral blood immune cell subsets, T-cell activation, and cytokines in septic patients - Xuan Lu; Cong-Ying Song; Ping Wang; Li Li; Li-Ying Lin; Shuai Jiang; Jia-Ning Zhou; Meng-Xiao Feng; Yun-Mei Yang; Yuan-Qiang Lu (Inflammation Research, 2024)

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Biotransformation of norethisterone by Rhizopus microsporus PT2906 - Xiulan Xin; Jia Liu; Shengqiao Luan; Meirong Zhou; Wenxin Wang; Yuzhuo Wu; Xiaochi Ma; Chao Wang; Ping Guo; Dawei Li (Phytochemistry Letters, 2023)

Predicting genetic response to future climate change in Eucalyptus grandis by combining genomic data with climate models - Ping Wang; Cuirong Jia; David Bush; Changpin Zhou; Qijie Weng; Fagen Li; Haiwen Zhao; Hairun Zhang (Forest Ecology and Management, 2023)

Source apportionment of water-soluble oxidative potential of PM2.5 in a port city of Xiamen, Southeast China - Jia-Min Li; Si-Min Zhao; Si-Han Xiao; Xiang Li; Shui-Ping Wu; Jie Zhang; James J. Schwab (Atmospheric Environment, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Effect of starvation on the performance of a biotrickling filter packed with diatomaceous earth composite fillers for xylene removal - Jia Liu; Shaojie Lu; Ping Li; Wenjun Liang (Process Safety and Environmental Protection, 2023)

Treating waste with waste: Facile KHCO3-modified calcium carbide slag for simultaneous removal of NO and SO2 - Fang Wang; Hui Li; Jiyun Gao; Chenhui Liu; Lijuan Jia; Jiayu Feng; Ping Ning (Fuel, 2023)

Tandem c-cl cleavage and oxidation over Pt/ZSM-5 catalysts for CH2Cl2 deep oxidation: Acidity – Redox synergy, rate – Limiting step, and catalyst stability - Yu-Kun Ma; Li-Li Xu; Long-Ren Ouyang; Lu-Lu Huang; Ai-Ping Jia; Yu Wang; Ji-Qing Lu (Chemical Engineering Journal, 2023)

A new sesquiterpenoid from the aconitum -derived fungus Aspergillus fumigatus M1 - Hao Ding; Jia-Peng Wang; Si-Ping Deng; Jun-Li Gan; Bing-Xian Li; Ling-Ling Yao; Sheng-Qi Zhang; Le Cai; Zhong-Tao Ding (Natural Product Research, 2023)

Impact of bentonite on greenhouse gas emissions during pig manure composting and its subsequent application - Jia-Ping Wu; Meng-Ling Li; Yan Wang; Shan Lin; Rong-Gui Hu; Rong-Biao Xiang (Journal of Environmental Management, 2023)

Fermentation of Rosa roxburghii Tratt by Limosilactobacillus fermentum NCU001464: Physicochemical characteristics and biological activity - Hai-Li Zhou; Fei Peng; Jia-Xin Lin; Li-Ping Hu; Mingyong Xie; Tao Xiong (Food Bioscience, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Prevalence and genomic analysis of t203-like G9 (G9-VI) rotaviruses circulating in children with gastroenteritis in Beijing, China - Hui-Jin Dong; Li-Ying Liu; Li-Ping Jia; Lin-Qing Zhao; Feng-Hua Jin; Lin Zhou; Yuan Qian (Archives of Virology, 2023)
Our previous surveillance revealed that t203-like G9 (tentatively designated subtype G9-VI) rotaviruses re-emerged in 2010 in Beijing and rapidly prevailed over the G9-III subtype (the most common G9 subtype globally) and previously predominant G genotypes over the following two years. G9-VI belongs to the VP7 evolutionary lineage VI, which includes unusual and sporadic human rotaviruses from China (t203) and Japan. To obtain insight into the epidemiology, evolution, and transmission advantages of G9-VI rotavirus, we performed follow-up surveillance (2014-2017) and whole-genome analysis of 12 representative G9 strains. The results showed that the G9 genotype was predominant (77.4%), with a marked increase in prevalence (previously 43.5%). Within the G9 genotype, subtype G9-VI accounted for the majority (98.3%) of cases. The most prevalent P-genotype was P[8] (93.7%), within which subtype P[8]b was rare (0.7%). Phylogenetically, the G9-VI subtype strains in this study clustered closely with contemporary emerging human rotaviruses from many other countries in VP7 lineage VI, indicating that this subtype is capable of spreading globally. These currently emerging G9-VI rotaviruses formed a distinct monophyletic subcluster when compared to early G9-VI rotaviruses. Furthermore, four specific amino acid substitutions and synonymous codon substitutions were observed in the VP7 genes between the current G9-VI and globally common G9-III rotaviruses. The remaining nine genes of all of the analyzed representative G9 strains, whether G9-VI or G9-III, combined with the P[8]a, P[8]b, or P[6] genotype and exhibited the same Wa-like backbone constellation.

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Ridge tillage increased halophyte fine root production and turnover rates by altering soil properties in an abandoned farmland in northwest China - Xu Zheng; Chao-qun Chen; Lu-hua Li; Jia-ping Wang (Rhizosphere, 2023)

Influence of hemin on structure and emulsifying properties of soybean protein isolate - Jiaming Zhang; Yangyang Jia; Wenjin Wu; Yingying Zhang; Ping Chen; Xiaofang Li; Xuetuan Wei; Chunmei Li; Kaikai Li (Food Chemistry, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Formation of secondary organic aerosols from the ozonolysis of Cis-3-hexenyl acetate: The effect of acidic seed particles and SO2 - Dalin Shi; Yi Chen; Jixing Liu; Gaosheng Zhao; Li Xu; Bin Jia; Ping Cheng (Atmospheric Environment, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Four new stilbenes and one new flavonoid with potential antibacterial and anti-SARS-CoV-2 activity from Cajanus cajan - Jia-Yan Chen; Xin Lian; Yu-Wen Fan; Zhuo-Yi Ao; Wei-Jie Zhang; Yong-Chen Pan; Li-Ping Chen; Jie Yuan; Jie-Wei Wu (Journal of Natural Medicines, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Study of polycyclic aromatic hydrocarbons accumulation in bioretention facilities and its influence on microbial community structure - Ya-jiao Li; Yan-ting Shi; Ling-zhi Zhao; Ya-fang Li; Jia-ping Wang; Jia-ke Li (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Construction of PES mixed matrix membranes incorporating ZnFe2O4 @MXene composites with high permeability and antifouling performance - Ping Zhou; Ting Wang; Chun-Hui Du; Guo-qin Wang; Li-guang Wu; Xiao-jia Jiang; Hai-Chang Guo (Journal of Environmental Chemical Engineering, 2023)

Environmental melamine exposure and adverse kidney outcomes in patients with type 2 diabetes mellitus - Yi-Chun Tsai; Chia-Fang Wu; Wei-Wen Hung; Ping-Shaou Yu; Chia-Chu Liu; Tusty-Jiuan Hsieh; Chu-Chih Chen; Sih-Syuan Li; Jia-Jen Chen; Yi-Wen Chiu; Shang-Jyh Hwang; Ming-Tsang Wu (Environmental Pollution, 2023)

Transcriptomics integrated with metabolomics unravels the interweaving of inflammatory response and 1-stearoyl-2-arachidonoyl-sn-glycerol metabolic disorder in chronic cadmium exposure-induced hepatotoxicity - Rongrong Hao; Heng Xiao; Hui Wang; Ping Deng; Yang Yue; Jingdian Li; Yan Luo; Li Tian; Jia Xie; Mengyan Chen; Zhou Zhou; Fengqiong Chen; et al. (Environmental Toxicology and Pharmacology, 2023)

Preparation of carbon foam from depolymerization-reforming lignin for capacitive deionization - Chun-Ping Li; Ya-Qi Wu; Jia-Jia An; Li-Xin Gao; Da-Quan Zhang; Jin Li; Zhong-Xun An (Desalination, 2023)

A time-series InSAR processing chain for wide-area geohazard identification - Zhike Zhang; Ping Duan; Jia Li; Deying Chen; Kang Peng; Chengpeng Fan (Natural Hazards, 2023)

Irisin Attenuates Apoptosis Following Ischemia–Reperfusion Injury Through Improved Mitochondria Dynamics and ROS Suppression Mediated Through the PI3K/Akt/mTOR Axis - Ji-fei Liu; Gang Su; Li-xia Chen; Juan-ping Zhou; Juan Gao; Jia-jia Zhang; Qiong-hui Wu; Wei Chen; De-yi Chen; Zhen-chang Zhang (Molecular Neurobiology, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Contamination characteristics and source analysis of potentially toxic elements in dustfall-soil-crop systems near non-ferrous mining areas of Yunnan, southwestern China - Ying Luo; Zhe Wang; Zhen-Long Zhang; Jia-Qian Zhang; Qiu-Ping Zeng; Duan Tian; Chao Li; Feng-Yu Huang; Shu Chen; Li Chen (Science of The Total Environment, 2023)

Response spectra for transient pore-pressure in a sandy seabed under random waves: Frequency-filtering effect - Jia-Hao Yu; Fu-Ping Gao; Chang-Fei Li (Ocean Engineering, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Mining genes related to anthocyanin synthesis and regulation in different potato varieties based on comparative transcriptomics - En-fang Qi; Xiao-xia Jia; He-ping Lv; Wei Huang; Guo-hong Wen; Zhang Li; Jian-wu Li (Journal of Plant Biochemistry and Biotechnology, 2023)

An Explainable Machine-Learning Model to Analyze the Effects of a PCSK9 Inhibitor on Thrombolysis in STEMI Patients - Pengyu Zhao; Jia Zhou; Chang Liu; Zhaoying Li; Ping He; Chunjie Li; Jia Zhao; Yonghong Hou (Journal of Medical and Biological Engineering, 2023)

Investigation of the stability and failure mechanism of slopes in Xiyu conglomerate due to toe erosion - Qiang Zhang; Yanni Zheng; Chaojun Jia; Ping Sun; Wenxin Li (Bulletin of Engineering Geology and the Environment, 2023)

Effects of phosphorus fertilizer application rate on transformation processes of phosphorus fractions in the purple alluvial soil of a riparian zone - Li-ping He; Kai-tao Jia; Dan Liu; Ke-hong Wang; Lin-Yan Duan; Jun-jie Lin (Journal of Mountain Science, 2023)

Juvenile hormone regulates the photoperiodic plasticity of elytra coloration in the ladybird Harmonia axyridis - Jia‐Xu Li; Zhong Tian; Xing‐Feng Liu; Bei Li; Hao‐Min An; Colin S. Brent; Jia‐Lu Wang; Xiao‐Ping Wang; Wen Liu (Molecular Ecology, 2023)
Many animals, including insects, exhibit plasticity of body colour in response to environmental changes. Varied expression of carotenoids, major cuticle pigments, significantly contributes to body colour flexibility. However, the molecular mechanisms by which environmental cues regulate carotenoid expression remain largely unknown. In this study, we used the ladybird Harmonia axyridis as a model to investigate the photoperiodic‐responsive plasticity of elytra coloration and its endocrine regulation. It was found that H. axyridis females under long‐day conditions develop elytra that are much redder than those under short‐day conditions, resulting from the differential accumulation of carotenoids. Exogenous hormone application and RNAi‐mediated gene knockdown indicate that carotenoid deposition was directed through the juvenile hormone (JH) receptor‐mediated canonical pathway. Moreover, we characterized an SR‐BI/CD36 ( SCRB ) gene SCRB10 as the carotenoid transporter responding to JH signalling and regulating the elytra coloration plasticity. Taken together, we propose that JH signalling transcriptionally regulates the carotenoid transporter gene for the photoperiodic coloration plasticity of elytra in the beetles, which reveals a novel role of the endocrine system in the regulation of carotenoid‐associated animal body coloration under environmental stimuli.

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

First report of Fusarium foetens causing root rot on lavender (Lavandula angustifolia) in China - Xue-Jun Wei; Bing-Guo Jia; Xing Wang; Nan-Yang Li; Su-Na Wang; Li Li; Ai Zhang; Hao-Tian Zhang; Li-Ping Wang (Journal of Plant Pathology, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Shellfish-algal systems as important components of fisheries carbon sinks: Their contribution and response to climate change - Ruolan Jia; Ping Li; Chengzhuang Chen; Ling Liu; Zhi-Hua Li (Environmental Research, 2023)

Impacts of climate change on vicennial spatial behaviors of Trichiurus japonicus in the East China Sea - Yan Jin; Xing-Wei Yuan; Yi Zhang; Jian-sheng Li; Li-ping Yan; Zun-lei Liu; Jia-hua Cheng (Estuarine, Coastal and Shelf Science, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

Histone methyltransferase SETDB1 promotes osteogenic differentiation in osteoporosis by activating OTX2-mediated BMP-Smad and Wnt/β-catenin pathways - Lianying Hu; Zhen Cheng; Lunan Wu; Liangliang Luo; Ping Pan; Shujin Li; Qiyu Jia; Ning Yang; Bin Xu (Human Cell, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Molybdenum isotope evidence from restricted-basin mudstones for an intermediate extent of oxygenation in the late Ediacaran ocean - Zhaozhao Tan; Jinxiang Wu; Wanglu Jia; Jie Li; Brian Kendall; Jianzhong Song; Ping’an Peng (Chemical Geology, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Study on non-point source pollution characteristics under different spatial scales: a case study of Hanjiang River Basin, China - Ya-jiao Li; Jia-ping Wang; Zi-hang Zhang; Gai-rui Hao; Ya-fang Li; Jia-ke Li (Environmental Science and Pollution Research, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Deciphering the microbial community tolerance mechanism and alteration of antibiotic resistance genes during chloramphenicol wastewater treatment - Jia Zhou; Yan Chen; Wan-Xia Li; Jian-Hang Qu; Tian Chen; Yi-Ping Wang; Ning-Yu Geng (International Biodeterioration & Biodegradation, 2023)

Tracking and dating incipient melting of a new grouplet of primitive achondrites - Yun Jiang; Ye Li; Jia Liu; Qing Wang; Li-Ping Qin; Ke Zhu; Shiyong Liao; Zongjun Yin; Yongbo Peng; Piers Koefoed; Weibiao Hsu (Geochimica et Cosmochimica Acta, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Evaluation of Fe3O4-MnO2@RGO magnetic nanocomposite as an effective persulfate activator and metal adsorbent in aqueous solution - Mang Lu; Xue-jiao Wu; Chu-xing Wan; Qiu-ping Gong; Jia-xin Li; Shuang-shuang Liao; Yu-an Wang; Shu-hao Yuan (Environmental Science and Pollution Research, 2023)

Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Peng Tian Li; Ying Li; Ying Chen; Jia Xi Zhang; Zi Hao Luo; Yi Fan Zhang; Jing Jiang; Yi Lei Wang; Zi Ping Zhang; Yong Hua Jiang; Peng Fei Zou (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune responses is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc -TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker ( Larimichthys crocea ) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc -TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc- TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc -TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc -TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3 , IRF7 , ISG15, ISG56 , RSAD2 , and TNF-α were up-regulated under Lc -TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc -TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.

Resource utilization of hazardous solid waste blast furnace dust: Efficient wet desulfurization and metal recovery - Xuejin Yang; Binghua Xie; Fang Wang; Ping Ning; Kai Li; Lijuan Jia; Jiayu Feng; Futing Xia (Chemosphere, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Phytostabilization mitigates antibiotic resistance gene enrichment in a copper mine tailings pond - Xinzhu Yi; Ping Wen; Jie-Liang Liang; Pu Jia; Tao-tao Yang; Shi-wei Feng; Bin Liao; Wen-sheng Shu; Jin-tian Li (Journal of Hazardous Materials, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

Preparation of XCu@TiO2 adsorbent for high-efficient PH3 removal in anaerobic environment and evaluation of desulfurization activity of deactivated adsorbent - Lijuan Jia; Xuejin Yang; Kaiqiang Hu; Jiayu Feng; Fang Wang; Kai Li; Xin Sun; Fei Wang; Ping Ning (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Insights into the mechanism of elemental mercury removal via ferric chloride modified carbon Aerogel: An experimental and theoretical research - Jiachen Li; Tong Li; Fengting Li; Tao Jia; Jiang Wu; Sikai Wu; Yang Ling; Ping He; Xu Mao; Jie Dong (Chemical Engineering Journal, 2023)

Ball-milling as effective and economical process for biodiesel production under Kraft lignin activated carbon stabilized potassium carbonate - Ning Yang; Xueru Sheng; Liting Ti; Haiyuan Jia; Qingwei Ping; Ning Li (Bioresource Technology, 2023)

Smog chamber study of secondary organic aerosol formation from gas- and particle-phase naphthalene ozonolysis - Jixing Liu; Shuping Zhu; Teng Guo; Bin Jia; Li Xu; Jun Chen; Ping Cheng (Atmospheric Environment, 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

Spatial distribution and driving factors of sediment net nitrogen mineralization in riparian zone of the Three Gorges Reservoir - Kai-tao Jia; Li-ping He; Ke-hong Wang; Zhi-guo Yu; Li-jiao Liang; Zhuo-lin Yu; Jun-jie Lin (Journal of Mountain Science, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Ultrasonic-assisted stewing enhances the aroma intensity of chicken broth: A perspective of the aroma-binding behavior of fat - Jun Qi; Chuan-kang Jia; Wen-wen Zhang; Hui-min Yan; Qing-yuan Cai; Xiu-ning Yao; Kuo Xu; Ying Xu; Wen-ping Xu; Guo-yuan Xiong; Mei-qi Li (Food Chemistry, 2023)

Oral administration of Synechococcus sp. PCC7942 trans-vp19 and trans-vp (19+28) genes improve the immune and antioxidant capacity in Procambarus clarkii under white spot syndrome virus stress - Jia Yang; Xiao-Ping Chi; Man Li; Wen-hui He; Rui Jia; Pei-Min He (Fish & Shellfish Immunology, 2023)

Urea-modified Cu-based materials: Highly efficient and support-free adsorbents for removal of H2S in an anaerobic and dry environment - Jiayu Feng; Lijuan Jia; Fei Wang; Xin Sun; Ping Ning; Chi Wang; Yuan Li; Kai Li (Chemical Engineering Journal, 2023)

Temperature tolerant all-solid-state touch panel with high stretchablity, transparency and self-healing ability - Zhenglin Chen; Fang Li; Likun Zhang; Zhengyang Lei; Canhui Yang; Chufan Xiao; Lijin Lian; Xi Yuan; Gul Ijaz; Jia'e Yang; Zijun Lin; Yunfeng He; et al. (Chemical Engineering Journal, 2023)

Corrigendum to “CD44-targeted hyaluronic acid-curcumin prodrug protects renal tubular epithelial cell survival from oxidative stress damage” [Carbohydrate Polymers 193 (2018) 268–280] - Jing-Bo Hu; Shu-Juan Li; Xu-Qi Kang; Jing Qi; Jia-Hui Wu; Xiao-Juan Wang; Xiao-Ling Xu; Xiao-Ying Ying; Sai-Ping Jiang; Jian You; Yong-Zhong Du (Carbohydrate Polymers, 2023)

Transcriptome analyses reveal the effects of mixed saline–alkali stress on indoleacetic acid and cytokinins in Malus hupehensis Rehd. leaves - Xin-Liang Wang; Ling Peng; Jian Wang; Jing-Lei Liu; Jing-Jing Jia; Li-Ping Tang (Physiology and Molecular Biology of Plants, 2023)

Carnosic Acid Attenuates AβOs-Induced Apoptosis and Synaptic Impairment via Regulating NMDAR2B and Its Downstream Cascades in SH-SY5Y Cells - Wen-ying Liu; Yan Li; Yan Li; Ling-zhi Xu; Jian-ping Jia (Molecular Neurobiology, 2023)

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Abietane diterpenoids with neuroprotective activities from Phlegmariurus carinatus - Yang Liu; Qiang Wang; Dong-Kun Zheng; De Zhang; Zhen Xie; Jia-Wei Hu; Xin-Hua Xie; Jing Li; Shu-Ping Jiang (Natural Product Research, 2022)

Design and Evaluation of a Machine Integrating Ridge-Breaking, Fertilizing, and Ridging for Ratoon Sugarcane Without Intertillage - Shang-Ping Li; Jia-Feng Pan; Jia-Qin Zhong; Wei Li; De-Quan Yang; Qing-Gui Mo (Sugar Tech, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

A1 Adenosine Receptor Activation Inhibits P2X3 Receptor–Mediated ATP Currents in Rat Dorsal Root Ganglion Neurons - Jia-Wei Hao; Wen-Long Qiao; Qing Li; Shuang Wei; Xue-Mei Li; Ting-Ting Liu; Chun-Yu Qiu; Wang-Ping Hu (Molecular Neurobiology, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Complete genome analysis of a novel chuvirus from a southern green stink bug (Nezara viridula) - Peng-Peng Ren; Zhuang-Xin Ye; Sai-Nan Wang; Jun-Min Li; Jian-Ping Chen; Chuan-Xi Zhang; Jia-Bao Lu (Archives of Virology, 2022)

Comparative transcriptomic analysis and validation of the ovary and testis in the ridgetail white prawn (Exopalaemon carinicauda) - Shaoting Jia; Ling Jin; Jianjian Lv; Jiajia Wang; Jitao Li; Ping Liu; Jian Li (Frontiers in Marine Science, 2022)
The ridgetail white prawn, Exopalaemon carinicauda is an important cultured seawater species in China. As female E.carinicauda grows faster than males, it is significant to search for the differentially expressed genes (DEGs) between males and females. However, there is no public available E.carinicauda genome data, and genes related to E. carinicauda sex differences are unclear. In this study, the transcriptome sequencing for ovary and testis tissues of E. carinicauda were conducted, and 20,891 DEGs were identified including 11,709 up-regulated DEGs and 9,182 downregulated DEGs. The functional categories related to meiosis and reproduction were enriched as well as the steroidogenesis KEGG pathway was clustered. Furthermore, the genes related to male reproduction and cell cycle were dug out which were verified by real-time PCR. In addition, two-color fluorescent in situ hybridization result showed that foxj1b might play roles during early stage of the ovary development. Therefore, our result provides clues for the study of genes related to reproduction and sex difference in E.carinicauda .

Enhanced M-CSF/CSF1R Signaling Closely Associates with PrPSc Accumulation in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Ying Xia; Cao Chen; Jia Chen; Chao Hu; Wei Yang; Lin Wang; Lian Liu; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Qi Shi; Zhi-Bao Chen; et al. (Molecular Neurobiology, 2022)

Differential expression and functional analysis of circRNA in the ovaries of Yili geese at different egg-laying stages - Xiao-yu Zhao; Ying-ping Wu; Hai-ying Li; Yan Cao; Zhi-yong Mei; Jia-hui Li (Genes & Genomics, 2022)

Feasibility Studies of Nebulized SARS-CoV-2 Neutralizing Antibody in Mice and Cynomolgus Monkeys - Jilei Jia; Zhaojuan Yin; Xiao Zhang; Huimin Li; Dan Meng; Qianqian Liu; Hongfang Wang; Meng Han; Shixiang Suo; Yan Liu; Ping Hu; Chunyun Sun; et al. (Pharmaceutical Research, 2022)
Purpose Neutralizing antibodies, administrated through intravenous infusion, have shown to be highly efficacious in treating mild and moderate COVID-19 caused by SARS-CoV-2 infection in the lung. However, antibodies do not transport across the plasma-lung barrier efficiently, and up to 100 mg/kg dose was used in human causing significant supply and cost burdens. This study was to explore the feasibility of nebulized antibodies inhalation delivery as an alternative route. Methods HB27, a potent RBD-specific humanized monoclonal antibody (Zhu et al. in National Sci Rev. 8:nwaa297, 2020), showed excellent protection against SARS-CoV-2 in animal model and good safety profile in clinical studies. The pharmacokinetics and preliminary safety of HB27 administrated through the respiratory tract were studied in mice and cynomolgus monkeys here. Results At a single 5 mg/kg dose, the peak HB27 concentration in mice pulmonary epithelial lining fluid (ELF) reached 857.8 μg/mL, 670-fold higher than the PRNT 90 value of 1.28 μg/mL, and maintained above PRNT 90 over 240 h. In contrast, when administrated by intravenous injection at a 5 mg/kg dose, the antibody concentrations in mice ELF were below PRNT 90 value throughout, and were about 50-fold lower than that in the serum. In cynomolgus monkeys administrated with a single dose through inhalation, the antibody concentration in ELF remained high within 3 days. No drug-related safety concerns were observed in the studies. Conclusions The study demonstrated that nebulized neutralizing antibody delivery though inhalation could be a more efficient and efficacious alternative approach for treating COVID-19 and other respiratory infectious diseases, and warrants further evaluation in clinical studies.

Comprehensive Transcriptome Analysis of Tea Crabapple (Malus hupehensis Rehd.) Roots Subjected to Mixed Saline–Alkali Stress - Xin-Liang Wang; Ling Peng; Jian Wang; Jing-Jing Jia; Li-Ping Tang (Plant Molecular Biology Reporter, 2022)

Transport process and mechanism of the Hongshiyan rock avalanche triggered by the 2014 Ludian earthquake, China - Shi-lin Zhang; Yue-ping Yin; Hai-bo Li; Wen-pei Wang; Jia-wen Zhou (Landslides, 2022)

Mapping the spatial distribution of fossil geothermal manifestations and assessment of geothermal potential of the Tangyin rift, Southeast of Taihang Mountain in China - Joshua Mahwa; Da-jiang Li; Jian-hua Ping; Wei Leng; Jia-bo Tang; Dong-yun Shao (Journal of Mountain Science, 2022)
The spatial prediction of geothermal sites along the southeast side of Taihang Mountain in the Tangyin rift is a critical goal in the development of renewable energy resources in cities such as Hebi in Henan province, which has significant potential for geothermal energy production due to the existence of deep faults and Cenozoic volcano. The study aimed to delineate areas with high geothermal manifestations for detailed geothermal exploration and well-test drilling. To define favorable zones for geothermal potentiality, multi-source datasets were chosen to generate evidence thematic layers that demonstrate the distribution of geothermal anomalies such as geologic maps, structural maps, Land Surface Temperature maps (LST), and hydrothermal mineral alterations maps. The remote sensing and Geographical Information System (GIS) approaches were integrated to map fossil geothermal manifestations and appraise the promising geothermal zones from Landsat 8 OLI/TIRS and Advanced Spaceborne Thermal Emission and Reflection Radiometer-Digital Elevation Model (ASTER-DEM) dataset using the Analytic Hierarchy Process (AHP), which is one of the Mult-criteria Decision Making methods. Results show LST values ranging from 22.6°C to 45.4°C, with the highest values found along the faults and volcanic areas. The hydrothermal alteration minerals discriminated from band ratios of 4/2, 6/5, and 6/7 for iron oxide, ferrous minerals, and clays reveal the presence of high amount of montmorillonite and illite minerals along the faults and volcanoes which are related to hot fluid circulation from subsurface. Structural analysis shows that the major structural trend follows the NNE Tangdong and Tangxi faults, with high density on the west side of the Tangxi fault where there is good exposure of outcrop but less fault density on the east side due to sedimentation in a low land which may conceal geological structures. Lastly, all the thematic layers of geothermal factors were reclassified, ranked, and integrated by the weight overlay logic model based on the influence of geothermal suitability to map potential areas for geothermal resources whereby 5 zones were obtained ranging from very poor to very good. The promising potential sites are mostly found along the highly deep structures of the major Tangxi fault crosscutting the permeable lithology of carbonate rocks and around the Hebi volcanoes. The distribution of hot springs and geothermal wells of the Hebi field were correlated and verified against the potential geothermal anomalies map. The overall integrated method proposes an advanced technique for designing the Tangyin rift’s exploration plan and development actions for geothermal resources utilization, which can be used for exploration of any unveiling geothermal potential sites.

Sphingopyxis yananensis sp. nov., a novel 2-nitropropane degrading bacterium isolated from a microbial fermentation bed substrate - Chao-chao Zheng; Ying-ying Jiang; Tian-fei Yu; Jing Li; Jia-min Ai; Mai-ping Li; Xiao-dong Liu; Zhen-shan Deng (Archives of Microbiology, 2022)

Deepened snow loosens temporal coupling between plant and microbial N utilization and induces ecosystem N losses - Zhou Jia; Ping Li; Yuntao Wu; Pengfei Chang; Meifeng Deng; Luyin Liang; Sen Yang; Chengzhang Wang; Bin Wang; Lu Yang; Xin Wang; Zhenhua Wang; et al. (Global Change Biology, 2022)
Seasonal differences in plant and microbial nitrogen (N) acquisition are believed to be a major mechanism that maximizes ecosystem N retention. There is also a concern that climate change may interrupt the delicate balance in N allocation between plants and microbes. Yet, convincing experimental evidence is still lacking. Using a 15 N tracer, we assessed how deepened snow affects the temporal coupling between plant and microbial N utilization in a temperate Mongolian grassland. We found that microbial 15 N recovery peaked in winter, accounting for 22% of the total ecosystem 15 N recovery, and then rapidly declined during the spring thaw. By stimulating N loss via N 2 O emission and leaching, deepened snow reduced the total ecosystem 15 N recovery by 42% during the spring thaw. As the growing season progresses, the 15 N released from microbial biomass was taken up by plants, and the competitive advantage for N shifted from microbes to plants. Plant 15 N recovery reached its peak in August, accounting for 17% of the total ecosystem 15 N recovery. The Granger causality test showed that the temporal dynamics of plant 15 N recovery can be predicted by microbial 15 N recovery under ambient snow but not under deepened snow. In addition, plant 15 N recovery in August was positively correlated with and best explained by microbial 15 N recovery in March. The lower microbial 15 N recovery under deepened snow in March reduced plant 15 N recovery by 73% in August. Together, our results provide direct evidence of seasonal differences in plant and microbial N utilization that are conducive to ecosystem N retention; however, deepened snow disrupted the temporal coupling between plant–microbial N use and turnover. These findings suggest that changes in snowfall patterns may significantly alter ecosystem N cycling and N‐based greenhouse gas emissions under future climate change. We highlight the importance of better representing winter processes and their response to winter climate change in biogeochemical models when assessing N cycling under global change.

The α5-nAChR/PD-L1 axis facilitates lung adenocarcinoma cell migration and invasion - Ping Zhu; Guiyu Kang; Yang Jiao; Chengzhi Gui; Huiping Fan; Xiangying Li; Yanfei Jia; Lulu Zhang; Xiaoli Ma (Human Cell, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

CaMKIIα Signaling Is Required for the Neuroprotective Effects of Dl-3-n-Butylphthalide in Alzheimer’s Disease - Bing-qiu Li; Ling-zhi Xu; Fang-yu Li; Ying Li; Yu Zhao; Heng Zhang; Mei-na Quan; Jian-ping Jia (Molecular Neurobiology, 2022)

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Discriminative optimization algorithm with global–local feature for LIDAR point cloud registration - Jia Wang; Ping Wang; Biao Li; Ruigang Fu; Siyi Zhao; Hong Zhang (International Journal of Remote Sensing, 2021)

Bacterial Community Structure and Diversity in the Aqueous Environment of Shihou Lake and its Relationship with Environmental Factors - Ru Deng; Xi Chen; Li-Ping Qiu; Jia-Zhang Chen; Shun-Long Meng (Indian Journal of Microbiology, 2021)

Astaxanthin Ameliorates Blood Pressure in Salt-Induced Prehypertensive Rats Through ROS/MAPK/NF-κB Pathways in the Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Yan Zhang; Chen-Long Wang; Yi-Ming Lei; Jia-Yue Yu; Dong-Miao Zong; Kai-Li Liu; Dong-Dong Zhang; Ying Li; Hua Tian; Nian-Ping Zhang; et al. (Cardiovascular Toxicology, 2021)

Design and Evaluation of a Novel Transversal Double-bud Sugarcane Planter with Seed Pre-cutting - Jia-Qin Zhong; Li-Min Tao; Shang-Ping Li; Fang-Lan Ma; Yuan-Ling Chen (Sugar Tech, 2021)

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Taxonomic description of Pseudomonas rhizovicinus sp. nov., isolated from the rhizosphere of a desert shrub Haloxylon ammodendron - Ao-Lei He; Hui-Ru Li; Hui-Ping Li; Jing-Yi Gou; Jia Chen; Qi Zhao; Jin-Lin Zhang (Antonie van Leeuwenhoek, 2021)

A small attentional YOLO model for landslide detection from satellite remote sensing images - Libo Cheng; Jia Li; Ping Duan; Mingguo Wang (Landslides, 2021)

Genetic diversity of potato virus Y potato isolates from Shandong province, China - Meng-Ao Jia; Lu Wang; Ji-Wu Zhang; Yu-Shuang Guo; Xiang-Dong Li; Yan-Ping Tian (Journal of Plant Pathology, 2021)

Comparative analysis of sRNAs, degradome and transcriptomics in sweet sorghum reveals the regulatory roles of miRNAs in Cd accumulation and tolerance - Weitao Jia; Kangqi Lin; Tengxue Lou; Juanjuan Feng; Sulian Lv; Ping Jiang; Ze Yi; Xuan Zhang; Duoliya Wang; Zijing Guo; Yetao Tang; Rongliang Qiu; et al. (Planta, 2021)

Neuroprotective carbazole alkaloids from the stems and leaves of Clausena lenis - Gui Yan; Yu-Jie Li; Ying-Ying Zhao; Jia-Ming Guo; Wen-Hao Zhang; Ming-Ming Zhang; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Mutation of iPGAM using the CRISPR/Cas9 system affects pollen vitality and chlorophyll synthesis in Nicotiana tabacum - Lijing Liu; Ling Jia; Li Xu; Lele Deng; Ping Zhao; Wanli Zeng (Plant Biotechnology Reports, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Retraction Note to: Resibufogenin suppresses tumor growth and inhibits glycolysis in ovarian cancer by modulating PIM1 - Qian Li; Chuanwu Jiang; Yan Wang; Minghua Wei; Huijin Zheng; Yanqi Xu; Xuegang Xu; Fengyu Jia; Kai Liu; Gang Sun; Jianhua Zang; Ping Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

The Extraction of Built-up Areas in Chinese Mainland Cities Based on the Local Optimal Threshold Method Using NPP-VIIRS Images - Chen Li; Ping Duan; Mingguo Wang; Jia Li; Birong Zhang (Journal of the Indian Society of Remote Sensing, 2021)

Deepened snow cover alters biotic and abiotic controls on nitrogen loss during non-growing season in temperate grasslands - Zhou Jia; Ping Li; Yuntao Wu; Sen Yang; Chengzhang Wang; Bin Wang; Lu Yang; Xin Wang; Jing Li; Ziyang Peng; Lulu Guo; Weixing Liu; et al. (Biology and Fertility of Soils, 2021)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

Constraints of salinity- and sediment-induced stratification on the turbidity maximum in a tidal estuary - Ting Lu; Hao Wu; Fan Zhang; Jiasheng Li; Liang Zhou; Jianjun Jia; Zhanhai Li; Ya Ping Wang (Geo-Marine Letters, 2020)

Gnaq Protects PC12 Cells from Oxidative Damage by Activation of Nrf2 and Inhibition of NF-kB - Xin Sun; Guo-Ping Li; Pu Huang; Lu-Gang Wei; Jia-Zhi Guo; Li-Juan Ao; Di Lu; Shao-Chun Chen (NeuroMolecular Medicine, 2020)

Sandstorm weather is a risk factor for mortality in ischemic heart disease patients in the Hexi Corridor, northwestern China - Xinghui Li; Hui Cai; Xiaolan Ren; Jin He; Jia Tang; Ping Xie; Nan Wang; Fangfei Nie; Linfeng Lei; Chenchen Wang; Wenli Li; Jing Ma (Environmental Science and Pollution Research, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Fluorescence in situ hybridization of 35S rDNA sites and karyotype of wild Lilium (Liliaceae) species from China: taxonomic and phylogenetic implications - Yan-Ping Zhou; Zhong-Xuan Wang; Yun-Peng Du; Jie-Wen Li; Heng-bin He; Gui-Xia Jia (Genetic Resources and Crop Evolution, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Removal of SO2 and NOx from flue gas using mud-phosphorus slurry - Lijuan Jia; Zizhen Li; Qian Yu; Jiyun Gao; Chenhui Liu; Tiancheng Liu; Ping Ning; Fang Wang (Environmental Science and Pollution Research, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Antioxidant coumarin and pyrone derivatives from the insect-associated fungus Aspergillus Versicolor - Tian-Xiao Li; Dan-Dan Meng; Ying Wang; Jin-Lu An; Jia-Feng Bai; Xue-Wei Jia; Chun-Ping Xu (Natural Product Research, 2020)

Deepened winter snow cover enhances net ecosystem exchange and stabilizes plant community composition and productivity in a temperate grassland - Ping Li; Emma J. Sayer; Zhou Jia; Weixing Liu; Yuntao Wu; Sen Yang; Chengzhang Wang; Lu Yang; Dima Chen; Yongfei Bai; Lingli Liu (Global Change Biology, 2020)
Global warming has greatly altered winter snowfall patterns, and there is a trend towards increasing winter snow in semi‐arid regions in China. Winter snowfall is an important source of water during early spring in these water‐limited ecosystems, and it can also affect nutrient supply. However, we know little about how changes in winter snowfall will affect ecosystem productivity and plant community structure during the growing season. Here, we conducted a 5‐year winter snow manipulation experiment in a temperate grassland in Inner Mongolia. We measured ecosystem carbon flux from 2014 to 2018 and plant biomass and species composition from 2015 to 2018. We found that soil moisture increased under deepened winter snow in early growing season, particularly in deeper soil layers. Deepened snow increased the net ecosystem exchange of CO 2 (NEE) and reduced intra‐ and inter‐annual variation in NEE. Deepened snow did not affect aboveground plant biomass (AGB) but significantly increased root biomass. This suggested that the enhanced NEE was allocated to the belowground, which improved water acquisition and thus contributed to greater stability in NEE in deep‐snow plots. Interestingly, the AGB of grasses in the control plots declined over time, resulting in a shift towards a forb‐dominated system. Similar declines in grass AGB were also observed at three other locations in the region over the same time frame and are attributed to 4 years of below‐average precipitation during the growing season. By contrast, grass AGB was stabilized under deepened winter snow and plant community composition remained unchanged. Hence, our study demonstrates that increased winter snowfall may stabilize arid grassland systems by reducing resource competition, promoting coexistence between plant functional groups, which ultimately mitigates the impacts of chronic drought during the growing season.

Dynamic change of vegetation and its response to climate and topographic factors in the Xijiang River basin, China - Lu Jia; Zhan-bin Li; Guo-ce Xu; Zong-ping Ren; Peng Li; Yu-ting Cheng; Yi-xin Zhang; Bin Wang; Jia-xin Zhang; Shu Yu (Environmental Science and Pollution Research, 2020)

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

RETRACTED ARTICLE: Resibufogenin suppresses tumor growth and inhibits glycolysis in ovarian cancer by modulating PIM1 - Qian Li; Chuanwu Jiang; Yan Wang; Minghua Wei; Huijin Zheng; Yanqi Xu; Xuegang Xu; Fengyu Jia; Kai Liu; Gang Sun; Jianhua Zang; Ping Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Potential role of IL-37 signaling pathway in feedback regulation of autoimmune Hashimoto thyroiditis - Cui-Ping Ren; Li Sun; Feng-Chun Liu; Chun-Lin Zuo; Miao Liu; Wenda Gao; Ji-Jia Shen (Histochemistry and Cell Biology, 2019)

Comparative Serum Proteomic Analysis of the Effects of Sodium Selenate on a Mouse Model of Alzheimer’s Disease - Ping Chen; Li-Xiang Wang; Xiao-Jing Sui; Shui-Ming Li; Yong Wang; Qiong Liu; Jia-Zuan Ni (Biological Trace Element Research, 2019)

Correction to: Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Ya Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Serratia microhaemolytica sp. nov., isolated from an artificial lake in Southern China - Juan Wang; Min-Ling Zheng; Jian-Yu Jiao; Wei-Jia Wang; Shuai Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Aster dianchuanensis (Asteraceae, Astereae), a new species from Yunnan and Sichuan, China - Jia-Wei Xiao; Jun-Jie Liao; Wei-Ping Li (Kew Bulletin, 2019)

Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Yax Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

An image layer difference index method to extract light area from NPP/VIIRS nighttime light monthly data - Shuai Jiang; Jia Li; Ping Duan; Yadong Wei (International Journal of Remote Sensing, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

DAPK1: a Novel Pathology and Treatment Target for Alzheimer’s Disease - Ling-zhi Xu; Bing-qiu Li; Jian-ping Jia (Molecular Neurobiology, 2019)

Evolution of pore-size distribution of intact loess and remolded loess due to consolidation - Jia-Ding Wang; Ping Li; Yan Ma; Sai K. Vanapalli (Journal of Soils and Sediments, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Profiling of indole metabolic pathway in thermo-sensitive Bainong male sterile line in wheat (Triticum aestivum L.) - Qing Su; Jing Yang; Qing Yun Fu; Fei Yun Jia; Suo Ping Li; Yong Li; You Yong Li (Physiology and Molecular Biology of Plants, 2019)

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Hazard zoning of trunk highway slope disasters: a case study in northern Shaanxi, China - Huan Zhao; Wei-Ping Tian; Jia-chun Li; Bao-Cheng Ma (Bulletin of Engineering Geology and the Environment, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

Protective Effect of Moderate Exogenous Electric Field Stimulation on Activating Netrin-1/DCC Expression Against Mechanical Stretch-Induced Injury in Spinal Cord Neurons - Meili Liu; Chuanwei Yin; Zhengtai Jia; Kun Li; Zhifa Zhang; Yuchen Zhao; Xianghui Gong; Xiaoyu Liu; Ping Li; Yubo Fan (Neurotoxicity Research, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

Late Quaternary tectonic activity and shortening rate of the Beiluntai fault zone in the South Tianshan, Xinjiang, NW China - Yuan Yao; He-Ping Song; Jian-Bo Chen; Shuai Li; Hai-Liang Jia (Arabian Journal of Geosciences, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Effects of Rhizoma Alismatis extract on biochemical indices and adipose gene expression in oleic acid-induced hepatocyte injury in Jian carp (Cyprinus carpio var. Jian) - Jinliang Du; Rui Jia; Li-ping Cao; Weidong Ding; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2018)

Genome-wide genetic variation and comparison of fruit-associated traits between kumquat (Citrus japonica) and Clementine mandarin (Citrus clementina) - Tian-Jia Liu; Yong-Ping Li; Jing-Jing Zhou; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology, 2018)

Integrated in silico–in vitro screening of ovarian cancer peroxisome proliferator-activated receptor-γ agonists against a biogenic compound library - Gui-Lian Zhang; Feng-Ying Liu; Jing Zhang; Li-Ping Wang; Er-Xia Jia; Shi-Ming Lv (Medicinal Chemistry Research, 2018)

A Fluorescent Sensor of 3-Aminobenzeneboronic Acid Functionalized Hydrothermal Carbon Spheres for Facility Detection of L-tryptophan - Rui Zhang; Li-Xia Wang; Yun-Di Zhang; Chun-Hua Ge; Jia-Ping Wang; Ying Zhang; Xiang-Dong Zhang (Journal of Fluorescence, 2018)

Mfn2-Mediated Preservation of Mitochondrial Function Contributes to the Protective Effects of BHAPI in Response to Ischemia - Xiao-Li Chen; Guo-Ping Zhang; Sheng-Long Guo; Jia-Qi Ding; Jia-Ji Lin; Qian Yang; Zhu-Yi Li (Journal of Molecular Neuroscience, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

HMGB1 attenuates TGF-β-induced epithelial–mesenchymal transition of FaDu hypopharyngeal carcinoma cells through regulation of RAGE expression - Yanmei Li; Ping Wang; Jia Zhao; Haonan Li; Dahai Liu; Wei Zhu (Molecular and Cellular Biochemistry, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Effects of salinity on simultaneous reduction of perchlorate and nitrate in a methane-based membrane biofilm reactor - Yin Zhang; Jia-Xian Chen; Li-Lian Wen; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Equilibrium and kinetic modeling of iron adsorption and the effect by chloride, sulfate, and hydroxyl: evaluation of PVC-U drinking pipes - Jia -Ying Wang; Shu-Ping Li; Kun-Lun Xin; Tao Tao (Environmental Science and Pollution Research, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

Tight regulation of the interaction between Brassica napus and Sclerotinia sclerotiorum at the microRNA level - Jia-Yi Cao; You-Ping Xu; Li Zhao; Shuang-Sheng Li; Xin-Zhong Cai (Plant Molecular Biology, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Acne-Like Subcutaneous Phaeohyphomycosis Caused by Cladosporium cladosporioides: A Rare Case Report and Review of Published Literatures - Ya Bin Zhou; Ping Chen; Ting Ting Sun; Xing Jia Wang; Dong Ming Li (Mycopathologia, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

The relationships between heart rate deceleration capacity and spectral indices of heart rate variability during different breathing frequencies - Yong-Ping Wang; Terry B. J. Kuo; Jia-Yi Li; Chun-Ting Lai; Cheryl C. H. Yang (European Journal of Applied Physiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Expression, purification and characterization of a thermostable leucine dehydrogenase from the halophilic thermophile Laceyella sacchari - Wenjun Zhu; Yan Li; Honghua Jia; Ping Wei; Hua Zhou; Min Jiang (Biotechnology Letters, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Feeding ecology of the mud shrimp S olenocera melantho in the E ast C hina S ea - Hui Yu Li; Jian Zhong Ling; Li Ping Yan; Jia Hua Cheng; Fen Hu (Marine Ecology, 2016)
The feeding habits of the mud shrimp Solenocera melantho were studied in the East China Sea by analysing 720 stomach contents and comparing diet composition and prey diversity among seasons, sexes and size classes. Feeding activity was linked to season and ovarian condition. The stomach fullness was high during spring and summer and low in fall. Females with advanced ovaries also displayed low stomach fullness, which suggests that feeding activity is affected by the reproductive cycle. The diet of S. melantho consisted of 42 different prey categories, primarily smaller crustaceans, Foraminifera, polychaetes, mollusks and fishes (larvae and eggs). Crustacea,Foraminifera and polychaetes together constituted the dominant prey groups, accounting for 75% of total prey abundance and >50% of total prey occurrence. Diet composition differed among seasons between sexes and size classes. Females and males consumed the same prey items but with different orders of importance. In terms of body size, the small shrimps preferred relatively small food items, such as Foraminifera and algae, whereas larger shrimps preferred polychaetes and crustaceans. Trophic diversity varied among the seasons within both sexes and size classes, with the highest values being observed in fall. Niche overlap was high within both sexes and size classes among seasons (0.6051–0.8740).

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Research on RTP aeromagnetic gradient data and its applicability in different latitudes - Lin Li; Hua Guo; Ping Wang; Wei-Jie Jia (Applied Geophysics, 2016)

Hyperspectral field estimation and remote-sensing inversion of salt content in coastal saline soils of the Yellow River Delta - Deyu An; Gengxing Zhao; Chunyan Chang; Zhuoran Wang; Ping Li; Tongrui Zhang; Jichao Jia (International Journal of Remote Sensing, 2016)

CD147 promotes IKK/IκB/NF-κB pathway to resist TNF-induced apoptosis in rheumatoid arthritis synovial fibroblasts - Yue Zhai; Bo Wu; Jia Li; Xi-ying Yao; Ping Zhu; Zhi-nan Chen (Journal of Molecular Medicine, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

A Study of 2,3,7,8-Tetrachlorodibenzo-p-dioxin Induced Liver Injury in Jian Carp (Cyprinus carpio var. Jian) Using Precision-Cut Liver Slices - Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Rui Jia; Guo-Jun Yin (Bulletin of Environmental Contamination and Toxicology, 2016)

Bioaccumulation and Elimination of the Herbicide Clomazone in the Earthworms Eisenia fetida - Jia Cao; Ping Li; Qing X. Li; Pengfei Zheng; Xiaoping Diao (Bulletin of Environmental Contamination and Toxicology, 2015)

Flavobacterium buctense sp. nov., isolated from freshwater - Xiao-Min Feng; Xu Tan; Li Jia; Ping-Ping Long; Lu Han; Jie Lv (Archives of Microbiology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Identification of volatile and softening-related genes using digital gene expression profiles in melting peach - Xiong-wei Li; Jun Jiang; Li-ping Zhang; Yi Yu; Zheng-wen Ye; Xiu-min Wang; Jing-yi Zhou; Ming-liang Chai; Hui-qin Zhang; Pere Arús; Hui-juan Jia; Zhong-shan Gao (Tree Genetics & Genomes, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Genetic polymorphisms of CYP2D6*10 and the effectiveness of combined tamoxifen citrate and testosterone undecanoate treatment in infertile men with idiopathic oligozoospermia - Kai-fa Tang; Yi-li Zhao; Shang-shu Ding; Qi-fei Wu; Xing-yang Wang; Jia-qi Shi; Fa Sun; Jun-ping Xing (Journal of Zhejiang University-SCIENCE B, 2015)

Lead accumulation and tolerance of Moso bamboo (Phyllostachys pubescens) seedlings: applications of phytoremediation - Dan Liu; Song Li; Ejazul Islam; Jun-ren Chen; Jia-sen Wu; Zheng-qian Ye; Dan-li Peng; Wen-bo Yan; Kou-ping Lu (Journal of Zhejiang University-SCIENCE B, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Neuropeptide trefoil factor 3 attenuates naloxone-precipitated withdrawal in morphine-dependent mice - Ping Wu; Hai-Shui Shi; Yi-Xiao Luo; Ruo-Xi Zhang; Jia-Li Li; Jie Shi; Lin Lu; Wei-Li Zhu (Psychopharmacology, 2014)

The source apportionment of polycyclic aromatic hydrocarbons (PAHs) in the topsoil in Xiaodian sewage irrigation area, North of China - Jia-Le Li; Yan-Xin Wang; Cai-Xiang Zhang; Yi-Hui Dong; Bin Du; Xiao-Ping Liao (Ecotoxicology, 2014)

Multiple correlations of mRNA expression and protein abundance in human cytokine profile - Hong-wu Du; Guang-yu Chen; Chun-he Yang; Chuan-bao Li; Yi-ping Xun; Jia Liu; Peng Chen; Li-li Shi (Molecular Biology Reports, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Wnt-promoted Isl1 expression through a novel TCF/LEF1 binding site and H3K9 acetylation in early stages of cardiomyocyte differentiation of P19CL6 cells - Huafei Lu; Yanming Li; Yang Wang; Yinan Liu; Weiping Wang; Zhuqing Jia; Ping Chen; Kangtao Ma; Chunyan Zhou (Molecular and Cellular Biochemistry, 2014)

Positive matrix factorization as source apportionment of soil lead and cadmium around a battery plant (Changxing County, China) - Jian-long Xue; Yu-you Zhi; Li-ping Yang; Jia-chun Shi; Ling-zao Zeng; Lao-sheng Wu (Environmental Science and Pollution Research, 2014)

High-level soluble expression of the hemA gene from Rhodobacter capsulatus and comparative study of its enzymatic properties - Jia-wei Lou; Li Zhu; Mian-bin Wu; Li-rong Yang; Jian-ping Lin; Pei-lin Cen (Journal of Zhejiang University-SCIENCE B, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Morphological and molecular evidence for a new species of Rhodotus from tropical and subtropical Yunnan, China - Li-Ping Tang; Yan-Jia Hao; Qing Cai; Bau Tolgor; Zhu L. Yang (Mycological Progress, 2014)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Requests for Health Education from Chinese Cancer Patients During Their Recovery Period: a Cross-Sectional Study - Wei-Li Qiu; Pei-Juan Lin; Fei-Qun Ruan; Xiao Wu; Miao-Ping Lin; Lian Liu; Jia-Yi Luo; Kun Lin (Journal of Cancer Education, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Association of TGF-β1 +869C/T promoter polymorphism with susceptibility to autoimmune diseases: a meta-analysis - Li Zhang; Jun-wei Yan; Ying-Xin Wang; Ya-nan Wan; Jian-ping Li; Ping Liu; Bin Xu; Bing-xiang Wang; Wen-jia Peng; Fa-ming Pan; Jing Wang (Molecular Biology Reports, 2013)

MJO change with A1B global warming estimated by the 40-km ECHAM5 - Ping Liu; Tim Li; Bin Wang; Minghua Zhang; Jing-jia Luo; Yukio Masumoto; Xiaocong Wang; Erich Roeckner (Climate Dynamics, 2013)

Geochemistry and Sr–Nd–Pb–Hf isotopic composition of the Donggou Mo-bearing granite porphyry, Qinling orogenic belt, central China - Li Yang; Fukun Chen; Bing-Xiang Liu; Zhao-Ping Hu; Yue Qi; Jia-De Wu; Jian-Feng He; Wolfgang Siebel (International Geology Review, 2013)

Molecular characterization and phylogenetic analysis of infectious bursal disease viruses isolated from chicken in South China in 2011 - Di Liu; Xiang-Bin Zhang; Zhuan-Qiang Yan; Feng Chen; Jun Ji; Jian-Ping Qin; Hai-Yan Li; Jun-Peng Lu; Yu Xue; Jia-Jia Liu; Qing-Mei Xie; Jing-Yun Ma; et al. (Tropical Animal Health and Production, 2013)

Overexpression of MsALMT1, from the Aluminum-Sensitive Medicago sativa, Enhances Malate Exudation and Aluminum Resistance in Tobacco - Qi Chen; Kong-Huan Wu; Ping Wang; Jia Yi; Kun-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Involvement of large conductance Ca2+-activated K+ channel in laminar shear stress-induced inhibition of vascular smooth muscle cell proliferation - Xiaoling Jia; Jingyun Yang; Wei Song; Ping Li; Xia Wang; Changdong Guan; Liu Yang; Yan Huang; Xianghui Gong; Meili Liu; Lisha Zheng; Yubo Fan (Pflügers Archiv - European Journal of Physiology, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Negative transcriptional regulation of inflammatory genes by group B3 vitamin nicotinamide - Xiao-Ming Zhang; Yu-Ping Jing; Meng-Ying Jia; Li Zhang (Molecular Biology Reports, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

A Comparison of the Biological Activities of Human Osteoblast hFOB1.19 Between Iron Excess and Iron Deficiency - Guo-yang Zhao; Li-ping Zhao; Yin-feng He; Guang-Fei Li; Chao Gao; Kai Li; You-jia Xu (Biological Trace Element Research, 2012)

Phylogenetic resolution and systematics of the Asian tree frogs, Rhacophorus (Rhacophoridae, Amphibia) - Jia‐Tang Li; Yang Li; Robert W. Murphy; Ding‐Qi Rao; Ya‐Ping Zhang (Zoologica Scripta, 2012)
Li, J.T., Li, Y., Murphy, R.W., Rao, D.‐Q. & Zhang, Y.‐P. (2012). Phylogenetic resolution and systematics of the Asian tree frogs, Rhacophorus (Rhacophoridae, Amphibia). — Zoologica Scripta , 41 , 557–570. The treefrog genus Rhacophorus , a large genus with 80 species, has a wide range, occurring eastward from India to China, Japan, South‐east Asia, the Greater Sunda Islands and the Philippines. The phylogenetic relationships and taxonomic recognition of many species are very controversial. To stabilize the taxonomy, the phylogenetic relationships among about 52 species are investigated from 96 samples using mtDNA sequence data. Matrilineal relationships based on maximum likelihood and Bayesian inference methods resolve three well‐supported lineages (A, B and C), although the phylogenetic relationships among three lineages remain ambiguous. Analyses support recognition of two previously assigned subgenera, Leptomantis and Rhacophorus , and these correspond to lineages A and B, respectively. Given that we have three strongly supported lineages, that these lineages are morphologically distinct, and the constrained geographic distributions of these groups, we recognize each lineage as a taxon. Subgenus Leptomantis includes species mainly from Malaysia, Indonesia and the Philippines. Subgenus Rhacophorus contains a mix of species occurring in India, Indochina and southern China. Lineage C accommodates species distributed mostly in East Asia, including Japan and China. Based on genetic and morphological data from type localities, the taxonomic recognition of some species needs to be reconsidered. Rhacophorus pingbianensis and Polypedates spinus are considered as junior synonyms of Rhacophorus duboisi . Specimens of Rhacophorus rhodopus from Vietnam and Hainan, China likely represent an undescribed, cryptic species.

Influence of UDP-glucuronosyltransferase polymorphisms on valproic acid pharmacokinetics in Chinese epilepsy patients - Xiao-Man Chu; Li-Fang Zhang; Guang-Ji Wang; Shen-Ning Zhang; Jia-Hui Zhou; Hai-Ping Hao (European Journal of Clinical Pharmacology, 2012)

Correlation between serum CA724 and gastric cancer: multiple analyses based on Chinese population - Xin-Zu Chen; Wei-Ke Zhang; Kun Yang; Lan-Lan Wang; Jin Liu; Li Wang; Jian-Kun Hu; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; Zong-Guang Zhou; Xian-Ming Mo (Molecular Biology Reports, 2012)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Construction of EGFP-Labeling System for Visualizing the Infection Process of Xanthomonas axonopodis pv. citri in planta - Li-Ping Liu; Zi-Niu Deng; Jin-Wang Qu; Jia-Wen Yan; Vittoria Catara; Da-Zhi Li; Gui-You Long; Na Li (Current Microbiology, 2012)

Genetic characterization of Aleutian mink disease viruses isolated in China - Yanwu Li; Juan Huang; Yun Jia; Yijun Du; Ping Jiang; Rui Zhang (Virus Genes, 2012)

Highly Sensitive Detection of Residual Chlorpromazine Hydrochloride with Solid Substrate Room Temperature Phosphorimetry - Jia-Ming Liu; Li-ping Lin; Xin-Xing Wang; Xuan Lin; Ping Zhou; Shao-Qin Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2012)

Prevention and treatment of allergic inflammation by an Fcγ-Der f2 fusion protein in a murine model of dust mite-induced asthma - Li-hui Lin; Ping Zheng; John W. M. Yuen; Juan Wang; Juan Zhou; Cun-quan Kong; Xia Peng; Jia Li; Li Li (Immunologic Research, 2012)

Identification of a new Bombyx mori nucleopolyhedrovirus and analysis of its bro gene family - Jing-Bo Zhou; Xing-Qi Li; Wanchai De-Eknamkul; Siripuk Suraporn; Jia-Ping Xu (Virus Genes, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Genetic polymorphism analysis of killer cell immunoglobulin-like receptor genes in the Chinese Uygur population - Hong-dan Wang; Bo-feng Zhu; Chun-mei Shen; Guo-lian Yuan; Guang Yang; Juan-ning Guo; Jiang-wei Yan; Hai-xia Qin; Jian-xin Guo; Li-ping Zhang; Xiao-qin Jia; Rudolf Lucas (Molecular Biology Reports, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

Molecular characterization of two recombinant potato virus Y isolates from China - Biao Wang; Jin-Lei Jia; Xiao-Qiang Wang; Zhen-Yu Wang; Bing-Hui Yang; Xiang-Dong Li; Xiao-Ping Zhu (Archives of Virology, 2012)

Microsporogenesis, microgametogenesis, and pollen morphology of Ambrosia artemisiifolia L. in China - Jia-Xi Liu; Min Wang; Bing-Xiao Chen; Ping Jin; Jing-Yu Li; Ke Zeng (Plant Systematics and Evolution, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Escherichia coli induces apoptosis in human monocytic U937 cells through the Fas/FasL signaling pathway - Jia-He Wang; Yang Peng; Li-Li Yang; Yi-Bing Wang; Bao-Gang Wu; Yi Zhang; Ping He (Molecular and Cellular Biochemistry, 2011)

The investigation of the interaction between ribavirin and bovine serum albumin by spectroscopic methods - Xing-Jia Guo; Ai-Jun Hao; Xiao-Wei Han; Ping-Li Kang; Yu-Chun Jiang; Xiang-Jun Zhang (Molecular Biology Reports, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

Lubricin: a novel potential biotherapeutic approaches for the treatment of osteoarthritis - Jia-peng Bao; Wei-ping Chen; Li-dong Wu (Molecular Biology Reports, 2011)

Effects of the crude extract of Polygala tenuifolia Willd on human sperm in vitro - Yi Qiu; Lei-guang Wang; Yi-fang Jia; Dan-tong Yang; Mei-hua Zhang; Yan-ping Zhang; Li-hong Zhang; Ling Gai (Journal of Zhejiang University-SCIENCE B, 2011)

Lack of association between methylenetetrahydrofolate reductase gene A1298C polymorphism and breast cancer susceptibility - Li-Xin Qiu; Jian Zhang; Wen-Hua Li; Qun-Ling Zhang; Hui Yu; Bi-Yun Wang; Lei-Ping Wang; Jia-Lei Wang; Hui-Jie Wang; Xiao-Jian Liu; Zhi-Guo Luo; Xiang-Hua Wu (Molecular Biology Reports, 2011)

Minimally-invasive treatment of communicating hydrocephalus using a percutaneous lumboperitoneal shunt - Lu Jia; Zhong-xin Zhao; Chao You; Jia-gang Liu; Si-qing Huang; Min He; Pei-gang Ji; Jie Duan; Yi-jun Zeng; Guo-ping Li (Journal of Zhejiang University-SCIENCE B, 2011)

Twenty-four polymorphic microsatellite markers from spotted barbell (Hemibarbus maculates) - Jun-Jie Zhu; Shi-Li Liu; Ke-Yi Ma; Jia-Le Li; Qing-Ping Lian (Conservation Genetics Resources, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Alleviation of osteoarthritis by Trichostatin A, a histone deacetylase inhibitor, in experimental osteoarthritis - Wei-Ping Chen; Jia-Peng Bao; Peng-Fei Hu; Jie Feng; Li-Dong Wu (Molecular Biology Reports, 2010)

Proteomics analysis of plasma membrane from liver sinusoidal endothelial cells after partial hepatectomy by an improved two-dimensional electrophoresis - Xuanwen Li; Li Xiong; Chunliang Xie; Jia Cao; Huobao Deng; Yong Lin; Rui Cao; Jianglin Li; Ping Chen; Songping Liang (Molecular and Cellular Biochemistry, 2010)

Leptin plays a catabolic role on articular cartilage - Jia-peng Bao; Wei-ping Chen; Jie Feng; Peng-fei Hu; Zhong-li Shi; Li-dong Wu (Molecular Biology Reports, 2010)

A New Phosphorimetry for the Determination of Trace Alkaline Phosphatase Using Multi-wall Carbon Nanotubes and Its Diagnosis of Human Diseases - Jia-Ming Liu; Ying Rao; Li Chen; Xin-Xing Wang; Li-Ping Lin; Chang-Qing Lin; Li-Hong Zhang; Ying Ou-Yang (Journal of Fluorescence, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Cloning and Characterization of p8 Homolog cDNA in the Atlantic Halibut (Hippoglossus hippoglossus) - Jia-Qing Wang; Lin-Chun Li; Sheng-Guo Lin; Zhi-Ping Wang (Biochemical Genetics, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Enhancing viability of two biocontrol yeasts in liquid formulation by applying sugar protectant combined with antioxidant - Jia Liu; Shi-Ping Tian; Bo-Qiang Li; Guo-Zheng Qin (BioControl, 2009)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

Molecular Cloning, Expression, and Chromosomal Mapping of the Porcine CDC-2-Like Kinase 1 (CLK1) Gene - Shui Hua Xie; Jia Qi Li; Yao Sheng Chen; Ping Gao; Hao Zhang; Ze Yue Li (Biochemical Genetics, 2009)

Isolation and Characteristics of the CN Gene, a Tobacco Mosaic Virus Resistance N Gene Homolog, from Tobacco - Gai-Yun Zhang; Ming Chen; Jia-Ming Guo; Tong-Wen Xu; Lian-Cheng Li; Zhao-Shi Xu; You-Zhi Ma; Xue-Ping Chen (Biochemical Genetics, 2009)

Limestone Dissolution Induced by Fungal Mycelia, Acidic Materials, and Carbonic Anhydrase from Fungi - Wei Li; Peng-Peng Zhou; Li-Ping Jia; Long-Jiang Yu; Xue-Li Li; Min Zhu (Mycopathologia, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Increased pathogenesis and inflammation of airways from respiratory syncytial virus infection in T cell deficient nude mice - Juan Zhou; Xi-Qiang Yang; Zhou Fu; Xiao-Dong Zhao; Li-Ping Jiang; Li-Jia Wang; Yu-Xia Cui (Medical Microbiology and Immunology, 2008)

Vimentin is required for dengue virus serotype 2 infection but microtubules are not necessary for this process - Wei Chen; Na Gao; Jia-li Wang; Yan-ping Tian; Zong-tao Chen; Jing An (Archives of Virology, 2008)

OsCYT-INV1 for alkaline/neutral invertase is involved in root cell development and reproductivity in rice (Oryza sativa L.) - Liqiang Jia; Botao Zhang; Chuanzao Mao; Jinhui Li; Yunrong Wu; Ping Wu; Zhongchang Wu (Planta, 2008)

Purification and characterization of a thermostable uricase from Microbacterium sp. strain ZZJ4-1 - Lei Kai; Xiao-Hang Ma; Xue-Lai Zhou; Xiao-Ming Jia; Xia Li; Kang-Ping Guo (World Journal of Microbiology and Biotechnology, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Localization of a novel gene for congenital nonsyndromic simple microphthalmia to chromosome 2q11-14 - Hui Li; Jia-Xin Wang; Cheng-Ye Wang; Ping Yu; Qiang Zhou; Yong-Gang Chen; Lu-Hang Zhao; Ya-Ping Zhang (Human Genetics, 2008)

AtMTM1, a novel mitochondrial protein, may be involved in activation of the manganese-containing superoxide dismutase in Arabidopsis - Zhao Su; Mao-Feng Chai; Ping-Li Lu; Rui An; Jia Chen; Xue-Chen Wang (Planta, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Development of EST-SSR in foxtail millet (Setaria italica) - Xiao-Ping Jia; Yun-Su Shi; Yan-Cun Song; Guo-Ying Wang; Tian-Yu Wang; Yu Li (Genetic Resources and Crop Evolution, 2007)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Fast screening target sites for RNA interference using a cell-free system - Huang Mei; Jia Fang-Jun; Li Chong-Yong; Li Yi-Ping; Guo Li-He (Biotechnology Letters, 2005)